PCB2 improves porcine oocyte maturation by enhancing TZP-mediated cumulus-oocyte communication - Yuwen Luo; Qingrui Zhuan; Dan Zhou; Hongyu Liu; Jun Li; Xiangwei Fu (Theriogenology, 2026)

New polyoxygenated fatty acid ester and other constituents from Dendrobium nobile Lindl. and their chemotaxonomic significance - Ting Chen; Dan Zhang; Xiujuan Fu; Siwei Chen; Hui Lei; Xiaoxu Bi (Biochemical Systematics and Ecology, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Hierarchical assembly of sub-1 nm nanowire for the construction of aerogels - Yuxiang Du; Xin Yang; Xiuqin Mei; Ran Du; Dan Liu; Changqing Miao; Rui Fu; Huazheng Sai (Chemical Engineering Journal, 2026)

A mechanically stable and kinetically optimized organic-inorganic hybrid SEI for ultra-long lifespan zinc metal anodes - Chenyi Cao; Dan Lu; Chao Li; Xin Tan; Tianci Li; Shoubin Zhou; Xueping Tang; Sean C. Smith; Zhao Fu; Hongjia Song; Yunya Liu; Xiangli Zhong; et al. (Chemical Engineering Journal, 2026)

Fabrication of microwave-absorbing MFe2O4@sepiolite (M = Mn, Mn0.5Ni0.5, Ni) nanorods with enhanced catalytic performance for degradation and assessment of intermediate toxicity - Ruolin Ni; Lei Jiang; Jinhui Lin; Dan Wu; Keming Zhang; Lu Fu; Zhaohong Zhang; Fang Ma; Yongcai Zhang (Applied Clay Science, 2026)

Ganocochlearcins A-P: Acyclic meroterpenoids from Ganoderma mushrooms targeting extracellular matrix remodeling in cancer-associated fibroblasts - Fu-Ying Qin; Dan Cai; Jiao-Jiao Zhang; Zhi-Yu Chen; Yong-Xian Cheng (Phytochemistry, 2026)

Pollution prediction of heating boiler plants based on data preprocessing and CNN-LSTM-attention model - Zhengda Lin; Jifeng Wang; Bingjie Yan; Zhe Fu; Liyan Liu; Dan Zhong; Xingwei Du; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

From agronomic performance to behavioral adoption of biochar‑based slow‑release fertilizer in saline‑alkali rice: A single‑season field trial and survey‑based SEM analysis - Zhixia Wang; Chang Dong; Junqiang Dong; Yang Cheng; Yuan Hu; Dan Liu; Yan Zhang; Zhen Qiu; Yanjiang Cai; Yongfu Li; Cheng Fu; Bing Yu (Journal of Environmental Chemical Engineering, 2026)

Synergistic vacuum steam pulse blanching and gliding arc cold plasma pretreatment enhances drying efficiency and folate retention in Yardlong bean pods - Samuel Ariyo Okaiyeto; Fan Yang; Dan Liu; Lei Fu; Shi-Han Yu; Xiao-Xiao Niu; Feng-Lun Zhang; Cheng Zhang; Feng-Kui Xiong; Mohsen Mokhtarian; Weiqiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Metal Bi-coupled chiral nanoscale structures enhance spin-polarized electrons to promote photocatalytic CO2 reduction - Dan Wu; Yanni Lang; Liang Xu; Qiyuexin Wang; Qiu Fu; Bingli Li; Xinye Zhao; Zhaoyi Yin; Yongjin Li; Dacheng Zhou; Yangke Cun; Zhiguo Song; et al. (Chemical Engineering Journal, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

Nitrogen dioxide exposure promotes CD8+T cell infiltration and contributes to increased susceptibility to ulcerative colitis: An integrative multi‑omics, artificial intelligence, and mouse model study - Zhijie Wang; Xin Chang; Tian Fu; Dan Xu; Yuanhong Ma; Hao Zhang; Hubin Xia; Xiaofeng Zhang; Yingdong Hou (Journal of Hazardous Materials, 2026)

CIDA: A context-informed decoupling approach for soil trace element estimation using spaceborne cross-sensor data - Yishan Sun; Dan Li; Hao Jiang; Kai Jia; Shuisen Chen; Chongyang Wang; Xingda Chen; Jing Zhang; Jinyue Chen; Xiao Zhang; Wenlin Fu; Weibin Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Double-crosslinked 2-HP-β-CD/SA hydrogels with Ca2+ for lemongrass essential oil encapsulation: Sprout inhibition and quality maintenance of potato tubers - Hou Qianqian; Yuan Dan; Chen Qingmin; Wang Jun; Fu Maorun; Kang Tingqiang (Food Bioscience, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Bi-doped SnO2 porous nanospheres for trace formaldehyde sensing at room temperature - Dan Meng; Yihang Fu; Lijun Li; Lei Zhang; Zongsheng Xie; Jian Qi; Xiaoguang San (Chemical Engineering Journal, 2026)

Synergistic engineering of oxygen vacancies and AuCu interface on ZnO for enhanced photocatalytic biomass valorization - Hao-Yu Chen; Wu-Dan Yang; Jie-Yang Dong; Ling-Bao Wu; Dan-Dan She; Ze-Kuan Zhang; Tian-Jun Gong; Qi Zhang; Yao Fu (Chemical Engineering Journal, 2026)

Synergistic SHH activation and BMP inhibition remodel progenitor niche for enhanced hair cell generation - Chunying Li; Dan He; Wenxu Tang; Liping Fu; Xilin Tan; Yao Yao; Xiaolei Yin (Science China Life Sciences, 2026)

Retraction notice to “Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study” [Sci. Total Environ. 883 (2023) 163662] - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2026)

Occurrence and distribution of short-chain chlorinated paraffins (SCCPs) in sediments from mariculture bays in northern China - Feiyao Lu; Junhui Chen; Dan Fu; Xueting Zhang; Haoshun Zhang; Tongzhu Han; Xiuping He (Regional Studies in Marine Science, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

Ocean acidification exacerbates UVR-induced inhibition of photosystem II and I in Corallina officinalis - Di Zhang; Zhengke Shen; Dan Hu; Jiazhen Sun; Futian Li; Li Gao; Feng Fu; Tao Jiang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Experimental and numerical investigations on the transport mechanisms of Ti3C2Tx MXene under variable flow and solution chemistry - Liyuan Fu; Tianxin Zhou; Yuxuan Yang; Guohui Yin; Yang Tang; Ziheng Zhang; Tiezhu Sun; Dan Zhou (Journal of Hazardous Materials, 2026)

Screening of typical pollutants in groundwater polluted by nitrogen heterocyclic pesticides and removal mechanism of iron-doped biochar - Renchuan Fu; Kai Liu; Dan Qu; Yuqi Qi; Xiaochen Qi; Chih-Huang Weng; Yanru Hao; Na Liu; Chunyu Wen (Journal of Environmental Sciences, 2026)

Development of an innovative in-situ solid-state fermentation system based on endophytic fungi and agrifood by-products pigeon pea roots to enhance genistein production - Jin-Xian Fu; Mo-Nan Wen; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Dan Qu (Innovative Food Science & Emerging Technologies, 2026)

A specific strategy for accelerating strength-development rate of self-generated proppants: the gel effect related autoacceleration - Xianyan Ren; Zhenyong Li; Yating Chen; Xiaoji Fu; Yirui Zhang; Dan Fang; Xirui Chen; Cheng Bian (Fuel, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Electrochemical degradation of benfuracarb using Mn-doped Ti4O7 ceramic membranes in water and wastewater - Zirui Luo; Shiyu Fu; Chuchu Wu; Bin Yao; Tian Qin; Jian Yang; Zongsu Wei; Yaoyu Zhou; Dan Zhi (Desalination, 2026)

A robust constrained-weight physics-informed neural network for forward and inverse analyses of mechanics - Kailin Ding; Yong Fu; Dan Fang (Computer Physics Communications, 2026)

Environmentally relevant doses of fluoride exposure mediate kidney injury by affecting Tregs/Teffs homeostasis - Bingshu Liu; Siqi Zhu; Dan Wei; Qiong Zhang; Guiyu Fu; Xiudian Li; Yanhui Gao; Wei Wei (Chemico-Biological Interactions, 2026)

Analysis of meteorological causes for a spring PM10 pollution episode over Hainan Island, China - Chuan-bo Fu; Li Dan; Jia-xiang Tang; Jin-he Tong (Atmospheric Research, 2026)

Hyperspectral phenotyping and GWAS identify novel QTLs for soybean photosynthetic rate - Li Wang; Ning Fu; Jinyu Zhang; Ao Shen; Yuanmeng Yu; Yanhong Wang; Xiaoli Guan; Dan Zhang; Fang Huang; Xiaoyong Yang; Deyue Yu; Zhongwen Huang; et al. (Theoretical and Applied Genetics, 2026)

Determination of short-chain chlorinated paraffins in marine sediment by automated online solid phase extraction coupled to liquid chromatography-high-resolution mass spectrometry - Feiyao Lu; Dan Fu; Xiuping He; Xueting Zhang; Haoshun Zhang; Tongzhu Han; Junhui Chen (Analytica Chimica Acta, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Influence of LED lighting on the cell growth, accumulation of bioactive flavonoids and terpenoids, antioxidant response, and photoreceptor-mediated light signal transduction in Ginkgo biloba L. callus cultures - Qing-Yan Gai; Jiao Jiao; Yu-Jie Fu; Hong-Yan Zhao; Xiao-Qing Wang; Dan Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

New alkaloids from the marine-derived fungus Penicillium sp. SWMU-WZ04-5 and their cytotoxic activity - Sijing Liu; Jinghao Cui; Mengyu Zhang; Ting Chen; Fengjian Lan; Xiujuan Fu; Siwei Chen; Dan Zhang; Ying Zhang; Hui Lei (Phytochemistry Letters, 2026)

Decoupling of Fe isotope and Fe3+/ΣFe in arc igneous rocks: Implications for crustal metasomatism and its contribution to mantle redox - Li-Tao Ma; Li-Qun Dai; Zi-Wei Yao; Zi-Fu Zhao; Ye-Dan Hu; Zhen-Wu Chen; Guo-Chao Sun (Geochimica et Cosmochimica Acta, 2026)

A new sesquiterpene and other constituents from Dendrobium nobile Lindl. and their chemotaxonomic significance - Wenyuan Zhou; Yi Yang; Xiaonan Li; Xiujuan Fu; Siwei Chen; Hui Lei; Ying Zhang; Dan Zhang; Chunlian Wu (Biochemical Systematics and Ecology, 2026)

Network toxicology and single-cell transcriptomics nominate candidate pyrethroid-associated targets and pathways in clear cell renal cell carcinoma - Fu Wen; Dan Wei; Wencai Wang; Zhonghua Sun; Zhipeng Xu; Jianning Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Decoding gibberellin–strigolactone interaction networks in cereal crops toward a next-generation Green Revolution - Jie Hu; Yunzhe Wu; Shuang Zhang; Qiaoling Zhang; Zhe Chai; Dan Li; Danlin Zhao; Binghui Wu; Xiuhua Gao; Xueying Liu; Kun Wu; Xiangdong Fu (Molecular Plant, 2026)

Achieving reversible dispersion and facile modification of dried cellulose nanocrystals using polyethylene glycol dimethyl ether as a superior capping agent - Yue Niu; Lulu Fu; Kaijie Liu; Huiqing Liu; Dan Zhang; Aoran Wang; Hongxiang Xie; Zhi Fan; Minjie Guo; Bowen Cheng (Food Hydrocolloids, 2026)

First investigation into occurrence, trophodynamics, and risk implication of polychlorinated naphthalenes and polychlorinated biphenyls in a terrestrial food chain from Tibetan Plateau - Siyuan Xiong; Wenxiao Pan; Duo Bu; Kai Huang; Boyuan Hu; Shuyi Shen; Qiangying Zhang; Zeng Dan; Xiaomei Cui; Yingming Li; Guorui Liu; Qinghua Zhang; et al. (Environmental Pollution, 2026)

Three-phase interface modulation strategy for SERS detection of pathogenic bacteria in complexed media - Sensen Zhou; Ruiqi Peng; Boyan Zhao; Yong Wang; Chen Fu; Wei Deng; Dan Li (Chemical Engineering Journal, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Pathway enrichment analysis of distinct regions of the Iceman’s stomach highlights heterogeneity of protein enrichment profiles - Zenan Wu; Dan Ju; Tianxiang Liu; Huiyun Rao; Qiaomei Fu (Science Bulletin, 2026)

Effect of the combination of lactic acid, ε-poly-L-lysine and sodium isoascorbate on the swelling, microbiomics variation, and quality attributes of vacuum-packed fresh cut lotus root - Jiahui Jiang; Qianlong Shi; Dan Li; Qingmin Chen; Cong Han; Jing Wei; Maorun Fu; Huaimei Cao; Xiaofei Xin (Postharvest Biology and Technology, 2026)

Resuscitation promoting factors enhance bioremediation of the petroleum contaminated saline alkaline soils by activating core microbiomes - Jianhui Fu; Jixiang Chen; Yonggang Wang; Tianfeng Wang; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

Novel dual-phase porous Mn2O3/(Co,Mn)(Co,Mn)2O4 composite cathode material with enhanced interfacial stability for ultra-long cycle life in zinc ion batteries - Haoran Wang; Zhaoxia Hou; Hui Zhang; Wensheng Zong; Shuting Yin; Haibo Long; Zhongchao Fu; Nan Wu; Zihui Zhai; Depeng Zhang; Fanshun Meng; Dan Zhou (Chemical Engineering Journal, 2026)

Genetic diversity of Theileria species identified from questing and parasitic ticks in selected areas in Qinghai, China - Yuan Han; Zhi Li; Yong Fu; Junlong Liu; Dan Jia; Chunhua Li; Hong Yin; Mengtong Lei (Veterinary Research Communications, 2026)

Effects of Lactobacillus Acidophilus Mediated Improvement of Intestinal Barrier in Mice with Autism - Yong Song; Jia Shi; XiaoYi Fu; Dan Fu; Li Xu; WeiMei Liu; JingJing Cao; YaoCheng Ding; ShuPeng Huang; Lin Zhou; Kai Qian (Probiotics and Antimicrobial Proteins, 2026)

COF-Zincon dual signal amplification: A sensitive real-time electrochemical sensor for Zn2+ detection towards anxiety disorder diagnosis - Honglong Zou; Yonggui Song; Jiaqi Shao; Bin Lai; Qinghui Fu; Zhifu Ai; Yali Liu; Yuhui Ping; Dan Su; Youhui Zhang; Huihui Liang (Analytica Chimica Acta, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

The role of the nasal microbiome in linking ozone pollution to allergic rhinitis in children - Hao Tang; Shuang Du; Yongqiang Tan; Wen Su; Zhiping Niu; Jin Sun; WenPu Shao; Xinyi Fang; Zhiwei Tang; Dongjun Zhang; Zhuoru Chen; Zhenhua Zhang; et al. (Journal of Hazardous Materials, 2026)

Solar-driven catalytic platforms for closed-loop carbon cycling: CO2 assisting biomass conversion - Jingwen Jiang; Yiheng Wang; Yuanjie Li; Junxi Huang; Weiping Zhang; Dan Wang; Dong Xu; Dong Fu; Pan Zhang; Lemeng Wang; Kun Zhao (Bioresource Technology, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

3D-printed fish-scale dam-like structured photothermal evaporators based on thiol-ene click chemistry for solar-driven freshwater production and salt recovery - Lixuan Yang; Xiaoyu Fu; Zhihan Xu; Feiyue Zhou; Jingxing Gui; Yuting Xue; Yuxuan Ma; Dan Yu; Wei Wang (Journal of Cleaner Production, 2026)

Source apportionment and uncertainty assessment of nitrate and phosphate pollution in shallow groundwater in agricultural watersheds based on multi-isotope methods - Qingfei Chen; Chi Wang; Anqiang Chen; Rongyang Cui; Wanli Hu; Bin Fu; Cunzheng Jiang; Xingwei Chen; Dan Zhang (Groundwater for Sustainable Development, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Tracing fertilizer transformation and leaching in karst soils via soil column experiments and nitrogen isotopes - Ping Zhang; Yi-Meng Ren; Xiao-Dan Wang; Fu-Jun Yue (CATENA, 2026)

Revealing the overlooking role of polysulfides in sulfide-based denitrification biofilms through mathematical modeling - Yan Yang; Yu Liu; Cong Fan; Huimin Fu; Mohamed S. Mahmoud; Kang Dan; Hongxiang Chai (Bioresource Technology, 2026)

Zoning-grading optimization of watershed ecological security network integrating function and structure: A case study in the Three Gorges Reservoir Area - Dan Chen; Kai-rui Guo; Wei Zeng; Fu-hai Wang (Journal of Cleaner Production, 2026)

Preparation of methyl salicylate nanoemulsion and its application in sprouting inhibition on potato tubers - Hou Qianqian; Wang Yixuan; Chen Qingmin; Fu Maorun; Yuan Dan (Food Chemistry, 2026)

Biodegradable microplastics exert differential impacts from polyethylene on pesticide fate in soil-earthworm systems: insights into degradation selectivity and microbial mechanisms - Dan Yang; Ruiting Dong; Furong Fu; Lixia Zhao; Xiaojing Li; Huike Ye; Mohan Bai; Yang Sun (Environmental Pollution, 2026)

Photothermal-activated self-healing MXene hydrogel for diabetic wound healing with polyphenol synergy - Siqi Ye; Dan He; Tao Chen; Keng-Fu Lan; Yongjin Zhong; Yancheng Lai; Yingying Wu; Anchun Mo (Chemical Engineering Journal, 2026)

Spermidine enhances cold tolerance in tomato fruit by boosting antioxidant and energy metabolism synergy - Jian-Lin He; Shi-Yin Xie; Xiao-Dan Zhao; Da-Qi Fu (Food Research International, 2025)

A peptidomics-based investigation of the synergistic effects of neutral and Alcalase proteases on release of antioxidant peptides from soybean protein isolates - Shulong Cai; Liqi Fan; Dan Liu; Changxing Wei; Na Yang; Xichao Fu; Rong Tang; Jucai Xu; Sheng Yin; Xin Chen (Food Chemistry, 2025)

Preparing both mechanically robust and highly conductive semi-solid supercapacitor using environment-friendly gelatin-based hydrogel with cellulose fibers and ionic liquid - Yunxia Yang; Dan Li; Ningguo Yang; Tengfei Yan; Yangbing Wen; Ning Yan; Fu Guo (Chemical Engineering Journal, 2025)

Activating graphitic carbon via a core/shell WO3/carbon architecture for electrocatalytic deactivation of dilute antibiotics - Wenyang Fu; Yanjun Yin; Jiahong Zou; Chunyang Dan; Shenbin Zheng; Huimin Sui; Yinan Liu; Yan Zou; Heng Shi; Guangming Jiang (Chemical Engineering Journal, 2025)

Morphology-controlled synthesis of WO3 nanosheet arrays/nanonet via in-situ solvothermal reactions for morphology-dependent N2H4/NO2 sensing performance at near room temperature - Yanan Fu; Ping Wang; Dan Zhao; Xiaojing Bai; Lijie Zhao; Lili Sui; Bing Zhao; Yan Jiang; Haixia Yu (Chemical Engineering Journal, 2025)

EDIL3 induced by GLIS2 suppresses the anti-tumor activity of CD8+ T cells and expedites epithelial-mesenchymal transition in thyroid cancer - Xu Qian; Bo Fu; Shuangfu Peng; Meiling Xue; Zhaohui Zhu; Dan Yao (Journal of Molecular Histology, 2025)

Late Cenozoic Climates and Mountains Drove Diversification of the Pardosa laura Species Complex From Eastern China - Li‐Juan Liu; Dan Fu; Shu‐Qiang Li; Yu‐Fa Luo (Journal of Biogeography, 2025)
Aim To test how evolutionary processes of spiders in mountain ranges of eastern China were in response to environmental changes, we analyze the correlation between diversification of the Pardosa laura species complex (Araneae, Lycosidae) and historical climates and mountains in this region. Methods We reconstruct phylogenetic relationships and patterns of phylogeography and genetic diversity using mtDNA data from samples spanning the full range of the species complex P. laura in eastern China. Results The P. laura species complex clustered into four lineages: Lineage I includes five haplotypes from the areas to the north of the Yinshan‐Yanshan Mountains; Lineage II consists of 23 haplotypes from the areas between the Qinling Mountains–Huaihe River Line and the Nanling Mountains; Lineage III and IV are composed of 21 and 62 haplotypes, respectively, from the areas between the Yinshan‐Yanshan Mountains and the Nanling Mountains. Each lineage corresponds to that, grouped from haplotype network analyses, with the same geographic distribution areas. All four lineages initially diversified during about 1.43 and 0.24 Ma ago (Ma) in relation to the Pleistocene glacial‐inglacial cycles. The biogeographic reconstructions suggest that the species complex P. laura most likely originated in central China around 7.68 (11.17–4.85) Ma in relation to the recent ( approximately 8 Ma) expansion of grasslands and retraction of forests. The inter‐colony dispersal between central China and northeastern China occurred during the late Neogene, between around 7.68 and 3.14 Ma. Central China is an important dispersal center, with dispersal to southwestern and northern China between the late Pliocene and middle Pleistocene, approximately 3.14–2.89 and 2.89–1.43 Ma, respectively. Main Conclusions The contemporary genetic structure of the P. laura species complex presents a high correlation between lineages and geographic distribution. The historical phylogeographic patterns suggested that the late Cenozoic climate changes and the mountainous corridors and isolation events, as well as the lineage dispersals and ecological adaptations shaped the diversification of a spider species complex in eastern China over long timescales.

Sustainable integrated synthesis of high-yield and high-purity lignin-derived carbon dots: Dual-functional fluorescence detection and efficient chromatographic separation of nitro-antibiotics - Yuanmin Gong; Dan Wang; Panpan Chen; Renyu Deng; Meiting Yan; Baian Ji; Lingling Liu; Xueping Tao; Zhining Xia; Qifeng Fu (Food Chemistry, 2025)

Thermal safety upgrading: Batch-to-flow transition of acid-catalyzed tert-butyl peroxypivalate synthesis - Dan Wei; Kai Ma; Lei Ni; Ahmed Mebarki; Gang Fu; Juncheng Jiang (Chemical Engineering Journal, 2025)

Evaluating green total factor productivity in Chinese port listed companies based on biased technological change perspective - Yuting Zheng; Xiongjun Yuan; Dan Liu; Jingying Tang; Huishan Fu (Environment, Development and Sustainability, 2025)

Electrocatalytic oxidation of ranitidine using a fluorinated blue titanium dioxide nanotube array electrode - Jianhui Xu; Zhijie Cui; Xin Fu; Dan Li; Yanyan Zeng; Yunfei Zhang; Peng Liu; Xiangteng Mo; Kexin Cao; Zijie Shen; Shangkun Ye (Journal of Environmental Chemical Engineering, 2025)

Survival strategies and transition mechanisms of Rhodococcus erythropolis KB1 to VBNC state under benzene stress - Jianhui Fu; Shiyuan Chen; Yonggang Wang; Tianfeng Wang; Jixiang Chen; Dan Luo (Journal of Environmental Chemical Engineering, 2025)

Influential mechanisms of light exposure on the reduction of V5+ by extracellular polymeric substances: Role of the reductive and nonreductive components - Wen Qing; Dan Zhou; Liyuan Fu; Tianxin Zhou; Haoran Xiong; Mengmeng Liang; Yi Huang; Jinshu Zhang; Yubin Li; Chengye Yang; Jingxian Qi (Journal of Environmental Chemical Engineering, 2025)

Impact of landscape configuration on water purification capacity: A case study in a plateau lakeside wetland - Jie Li; Dan Li; Yu Fu; Yu Huang; Xiaoyan Li; Binghui Zheng (Ecological Engineering, 2025)

Synergistic catalysis of CuxFey/CeO2 bimetallic catalysts for oxidative dehydrogenation of C2H6 with CO2 - Dan Guo; Zouxuan Qi; Zelong Fu; Zhenli Lv; Li Kang; Feigang Zhao; Tongrui Wan; Shengping Wang; Xinbin Ma (Chemical Engineering Journal, 2025)

Lithium bond-mediated multiple synergy enabling mechanical robustness, self-healing and ultrasensitive ion-conductive elastomers for flexible sensor - Lingli Kong; Tianwen Luo; Rufeng He; Dan Huang; Bai Huang; Lihua Fu; Baofeng Lin; Chuanhui Xu (Chemical Engineering Journal, 2025)

Multi-level metalized PBO composite fabric for polar extreme environments: integrating electromagnetic protection, stable electric thermal conversion, and high-strength - Che Zhou; Dan Yu; Canglong Xing; Zhichao Zhu; Zeyu Yang; Xinhai He; Tao Fu; Zhongxiao Song; Wei Fan; Dongzhen Chen (Chemical Engineering Journal, 2025)

Configuration-locked near-planar D-A-D polymers for ultrahigh stability electrochromic supercapacitors - Haichang Fu; Hongtao Fang; Junze Jin; Yicai Lu; Weijun Li; Qidi Huang; Yanxian Jin; Zhangxin Chen; Dan Chen; Kai Huang (Chemical Engineering Journal, 2025)

Molecular evolution of the bZIP family in allotetraploid Gossypium and GhbZIP017 function under drought stress - Fangting Ye; Jing He; Zhaowei Li; Huanyu Wu; Ziyou Zhang; Dan Fu; Yanchun Li; Jinwen Huang; Changlan Zhu; Kai Fan (Plant Cell Reports, 2025)

Multiomics approach towards the detoxification of cadmium in Fritillaria cirrhosa using citrulline and zinc oxide nanoparticles in Qinghai-Tibet’s ecosystems - Jialu Wang; Zemin Yang; Dan Gao; Haitao Liu; Haobo Zhang; Huigan Xie; Shaobing Fu; Xiwen Li (Journal of Hazardous Materials, 2025)

The influential mechanisms of solution chemistry on the stability and transport of vanadium-titanium magnetite tailing colloids - Qidi Zhao; Dan Zhou; Haoran Xiong; Liyuan Fu; Tianxin Zhou; Jianing Sun; Mingzheng Huang; Jinshu Zhang; Yubin Li; Chengye Yang; Yi Huang (Journal of Hazardous Materials, 2025)

Multi-objective interpretation machine learning framework for Synergistically optimizing energy consumption and surface quality in electrolytic copper foil production - Zhengwu Yang; Xinwan Zhang; Huawei Hu; Yaqi Shi; Wenxuan Xu; Huiting Huang; Wenzhuo Zhang; Dan Fu; Zhihao Lu; Daqing Jia; Dingming Chang; Lehua Zhang (Journal of Cleaner Production, 2025)

Transcriptomics revealed the regulatory mechanism of phenylalanine butyramide on the growth and biofilm formation of Lactobacillus paracasei - Xinyu Fan; Yize Li; Yin Fu; Pengcheng Chen; Dan Wu; Pu Zheng (Food Bioscience, 2025)

Assessment of abuse potential of furanylfentanyl and tetrahydrofuranylfentanyl - Yuanyuan Chen; Miaojun Lai; Xiangyu Li; Yanling Qiao; Deli Xu; Dan Fu; Bin Di; Peng Xu (Psychopharmacology, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Combining network pharmacology and RNA sequencing to reveal the mechanism of emodin for the treatment of human neuroblastoma - Hai-mei Jiang; Shang-yi Huang; Dan Huang; Yan Zhao; Yi Yuan; Hai-fu Huang; Ying Tang; Jin-fang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A hydrophobic cathode design towards high-stability Zn-air batteries: Coupling FeTAP molecules with self-supporting edge-rich graphene membrane - Jiachen Meng; Yulei Zhang; Xuemin Yin; Yanqin Fu; Dan Wen; Qiang Song; Hejun Li (Chemical Engineering Journal, 2025)

Lentiviral vectors for gene therapy of α-thalassemia - Saijuan Xu; Dan Liang; Yan Cheng; Gongrui Sun; Feiyan Zhao; Yang Yang; Haokun Zhang; Yongrong Lai; Bin Fu; Yuxuan Wu (Science China Life Sciences, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Preparation of hydrophilic and antibacterial nanofiltration membrane by post-grafting N-(3-Aminopropyl)-imidazole - Yu Fu; Fangbo Zhao; Yingzheng Liu; Ruiqi Li; Hongxu Chen; Liu Yang; Zhiguo Li; Mingcong Wu; Dan Wang (Journal of Environmental Chemical Engineering, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Breeding of lactic acid-tolerant Saccharomyces cerevisiae based on atmospheric and room temperature plasma technology and automatic high-throughput microbial microdroplet culture system - Haowei Fan; Yin Wan; Yixin Huang; Jayi Yuan; Jiahui Fan; Yaru Kou; Xuefeng Yu; Yufeng Pan; Dan Huang; Guiming Fu (Food Microbiology, 2025)

Protective effects of anthocyanins on the nervous system injury caused by fluoride-induced endoplasmic reticulum stress in rats - Dan Wei; Shiwen Tan; Shujuan Pang; Bingshu Liu; Qiong Zhang; Siqi Zhu; Guiyu Fu; Dianjun Sun; Wei Wei (Food and Chemical Toxicology, 2025)

Organic photothermal cocrystal directs Janus solar steam evaporator for efficient and scalable seawater desalination - Shouzhen Li; Chenfei Yang; Yi Su; Mengran Liu; Siyao Fu; Guangyao Zhao; Dan He; Lingjie Sun; Xiaotao Zhang; Wenping Hu (Chemical Engineering Journal, 2025)

Effects of shrub stem and litter on promoting concentrated flow branching, increasing flow resistance, and reducing sediment during gully bed erosion - Lin Liu; Donghong Xiong; Binyan Zhang; Wenduo Zhang; Suhua Fu; Liangtao Shi; Dan Yang; Baojun Zhang; Xiaodan Wang (CATENA, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

RalB promotes lymph node metastasis in tongue squamous cell carcinoma - Yuman Zhang; Jiali Yang; Yi Gong; Zhihan Liu; Yanguang Yang; Xiaoyong Song; Yuting Gao; Yajun Xiong; Dan Wang; Kai Fu; Lifeng Jia; Xinli Shi (Genes & Genomics, 2025)

Chemistry for water treatment under nanoconfinement - Wanyi Fu; Ziyao Liu; Dan Li; Bingcai Pan (Water Research, 2025)

Effectiveness and mechanism of using sodium alginate-magnesium silicate carrier in UASB reactor to resist shock loading of coking wastewater - Yi Jiang; Wenlai Xu; Yizhi Zhang; Ruoxi Yan; Yifei Xie; Dan Zhang; FengLin Jia; Linshan Yang; Shah Zaib; Ruiyang Li; Pan Li; Songyu Fu; et al. (Journal of Cleaner Production, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Ambient-temperature α-pinene hydrogenation to cis-pinane over Ru/CeO2-H catalyst via the dimethyl-up configuration - Yu-Xuan Fu; Shu-Yi Huang; Ming-Shuai Sun; Yan Zhou; Dan-Dan Cai; Wen-Shuai Zhu; Wei Hui; Duan-Jian Tao (Chemical Engineering Journal, 2025)

Soil and litter microbiomes as joint drivers of ecosystem multifunctionality in a 60-year-old forest plantation - Shu-Yi-Dan Zhou; Xu Li; Josep Peñuelas; David T. Tissue; Roy Neilson; Xujun Liu; Zhiyang Lie; Fu-Yi Huang; Junhua Yan; Dong Zhu; Juxiu Liu (Journal of Environmental Management, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Optimization of mechanical properties and finite element simulation analysis of hollow fiber membranes in gas-liquid membrane separation technology - Zhengda Lin; Yihe Wang; Zhe Fu; Dan Zhong; Xingwei Du; Jun Zhang (Desalination, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Equitable pathways for sustainable tuna fisheries management in the Indian Ocean - Alex Tidd; Patrice Guillotreau; Dan Fu; Iago Mosqueira; Laurent Dagorn; Manuela Capello (Marine Policy, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

Hypertonic stress affects the expression of clock protein CmFRQ in Cordyceps militaris and remodels the morphology of fruiting body - Jing-Mei Peng; Dan-Dan Zhang; Ming-Jia Fu (Biologia, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Catalytic degradation of ethyl acetate at room temperature over Ni/NAC monolithic catalyst - Xiangci Wu; Chenglong Dai; Lisheng Zhang; Ge Gao; Jiahui Shi; Dan Zhao; Bingfeng Fu; Shejiang Liu; Jianfeng Fu; Hui Ding (Journal of Environmental Chemical Engineering, 2025)

Dynamic transformation and leaching processes of nitrogen in a karst agricultural soil under simulated rainfall conditions - Ping Zhang; Fu-Jun Yue; Xiao-Dan Wang; Sai-Nan Chen (Journal of Contaminant Hydrology, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Origin of the coeval Nb-enriched and arc mafic igneous rocks: Implications for Paleozoic tectonic evolution of the Southwestern Tianshan - Li-Tao Ma; Li-Qun Dai; Ye-Dan Hu; Zi-Fu Zhao (Chemical Geology, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Historical air pollutant emissions and future sustainable pathways of global cement plants - Xizhe Yan; Dan Tong; Zhi Cao; Cuihong Chen; Yaqin Guo; Ruochong Xu; Xinying Qin; Yujia Fu; Yang Liu; Dongsheng Zheng; Kebin He; Qiang Zhang (Resources, Conservation and Recycling, 2024)

Metabolomics integrated with mass spectrometry imaging reveals novel action of tetramethylpyrazine in migraine - Ziwei Xing; Yu Chen; Junren Chen; Cheng Peng; Fu Peng; Dan Li (Food Chemistry, 2024)

Exposure to toluene diisocyanate induces dysbiosis of gut-lung homeostasis: Involvement of gut microbiota - Yuxuan Gou; Fu Lin; Li Dan; Dianyu Zhang (Environmental Pollution, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Shallow groundwater table fluctuations weaken nitrogen accumulation in the thin layer vadose zone of cropland around plateau lakes, Southwest China - Qingfei Chen; Anqiang Chen; Jinheng Min; Lin Li; Wanli Hu; Chi Wang; Bin Fu; Shufang Guo; Dan Zhang (Science of The Total Environment, 2024)

Corrigendum to “Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region” [J. Clean. Prod. 479 (2024) 144006] - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Two-way coupling fluid–structure interaction analysis on dynamic response of offshore wind turbine - Fen Li; Jiaojiao Fu; Jiahui Chen; Dan Hu (Marine Georesources & Geotechnology, 2024)

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

A collaborative governance model for electric vehicle charging infrastructure incorporating policy evaluation and feedback - Yiting Zhang; Henry J. Liu; Shuai Ling; Dan Wang; Yifan Fu; Xueqing Wang (Utilities Policy, 2024)

Enhancing safe and effective treatment of carbapenem-resistant Klebsiella pneumoniae with polymyxin B-loaded dendritic nanoparticles - Wen Zhong; Yuyin Fu; Xukun Liao; Na Xu; Lingyi Shen; Jinglin Wu; Dan Zheng; Yadi Zhou; Lin Tan; Binyi Xia; Xinghua Fan; Meng Zhou; et al. (Chemical Engineering Journal, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Spatiotemporal analysis of microstructure, sensory attributes, and full-spectrum metabolomes reveals the relationship between bitterness and nootkatone in Alpinia oxyphylla miquel fruit peel and seeds - Xiaolu Chen; Yong Yang; Maoyuan Wang; Qin Tian; Qian Jiang; Xuan Hu; Weiguo Ye; Wanyun Shen; Xueting Luo; Xueyan Chen; Chao Yuan; Dan Wang; et al. (Food Research International, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

A new 3D printing strategy by enhancing shear-induced alignment of gelled nanomaterial inks resulting in stronger and ductile cellulose films - Yunxia Yang; Dan Li; Ning Yan; Fu Guo (Carbohydrate Polymers, 2024)

Secular mantle wedge evolution due to variable slab fluid metasomatism: Evidence from Permian-Triassic mafic igneous rocks in the Paleo-Tethys tectonic regime - Ye-Dan Hu; Li-Qun Dai; Li-Tao Ma; Zi-Fu Zhao (Chemical Geology, 2024)

Research on the influence of injection strategies on the in-cylinder combustion process and emissions of methanol - Juan Yu; Feng Zhou; Jianqin Fu; Dan Huang; Chenghao Wu; Jingping Liu (Biomass and Bioenergy, 2024)

Management strategy evaluation operating model conditioning: a swordfish case study - Daniela Rosa; Iago Mosqueira; Dan Fu; Rui Coelho (Reviews in Fish Biology and Fisheries, 2024)
Evaluation of fish stock status is a key step for fisheries management. Tuna Regional Fisheries Management Organizations (t-RFMOs) are moving towards management strategy evaluation (MSE), a process that combines science and policy and depends on technical aspects, developed by scientists, designed to meet management objectives established by managers and other stakeholders. In the Indian Ocean, the current management advice for swordfish ( Xiphias gladius ) is based on an ensemble of 24 models considering four areas of uncertainty about the stock dynamics. There is an ongoing MSE process for swordfish, and this paper describes the methodology being applied for the conditioning of the operating model (OM), including model selection and validation. In the MSE, nine sources of uncertainty were considered, each being characterized by 2–3 levels. A partial factorial design was employed to reduce the number of models from a full factorial design to those needed to encompass the overall uncertainty. A selection and validation process was carried out, filtering models that converged, showed good predictive skills, and provided plausible estimates. Overall, the estimated spawning stock biomass (SSB) relative to SSB at maximum sustainable yield (MSY), and fishing mortality (F) relative to F MSY encompasses the estimates of the stock assessment ensemble at the most optimist area of the distribution. The MSE for swordfish is an ongoing process that is expected to provide more robust management advice in the future. Further developments to the OM can still occur, but the methods presented herein can be applied to this, or other species, MSE processes.

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Shallow groundwater table fluctuations promote the accumulation and loss of phosphorus from surface soil to deeper soil in croplands around plateau lakes in Southwest China - Qingfei Chen; Wenchao Li; Anqiang Chen; Jinheng Min; Wanli Hu; Chi Wang; Bin Fu; Dan Zhang (Journal of Environmental Management, 2024)

Impact of thermal ultrasound on enzyme inactivation and flavor improvement of sea cucumber hydrolysates - Yi-chao Cheng; Dan-li Jin; Wen-tao Yu; Bo-yang Tan; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Determination of chloropropanol esters and glycidyl esters in nutritional foods by gas chromatography–tandem mass spectrometry based on acid hydrolysis and solid-phase extraction - Yi Li; Dan Chen; Wusheng Fu; Yan Yang; Huafeng Chen; Lei Ni; Hongjing Chen; Dingguo Jiang; Sophia Zhang; Rongjuan Gui (Food Additives & Contaminants: Part A, 2024)

PKC-θ is an important driver of fluoride-induced immune imbalance of regulatory T cells/effector T cells - Siqi Zhu; Bingshu Liu; Guiyu Fu; Liu Yang; Dan Wei; Liwei Zhang; Qiong Zhang; Yanhui Gao; Dianjun Sun; Wei Wei (Science of The Total Environment, 2024)

First comprehensive assessment of dietary chlorinated paraffins intake and exposure risk for the rural population of the Tibetan Plateau, China - Wei Zhou; Duo Bu; Kai Huang; Qiangying Zhang; Xiaomei Cui; Zeng Dan; Yinzheng Yang; Yilin Fu; Qianyuan Yang; Yunhe Teng; Jie Fu; Aiqian Zhang; et al. (Science of The Total Environment, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Addressing redox shuttling in Li-O2 batteries: Mechanistic insights by synchrotron X–ray tomography - Dan Li; Fu Sun; Yuqing Zhang; Yulong Liu; Hao Sun; Haiming Xie; Jia Liu; Seung-Taek Myung; Jiefang Zhu (Chemical Engineering Journal, 2024)

The effect of fine particulate matter (PM2.5) pollution on health inequality: an intergenerational perspective - Dan Yan; Honglu Ji; Hong Fu; Jingjing Jiang; Bin Su; Bin Ye (Environmental Geochemistry and Health, 2024)

Transcriptomic profiling reveals color variation mechanism of Fritillaria cirrhosa for the molecular plant breeding - Ye Wang; Zemin Yang; Xinyue Wang; Ziyi Liu; Huigan Xie; Shaobing Fu; Dan Gao; Xiwen Li (Acta Physiologiae Plantarum, 2024)

The evolution and formation of centromeric repeats analysis in Vitis vinifera - Dan Pei; Xue Yu; Weihong Fu; Xuhui Ma; Jinggui Fang (Planta, 2024)

‘Drivin' with your eyes closed’: Results from an international, blinded simulation experiment to evaluate spatial stock assessments - Daniel R. Goethel; Aaron M. Berger; Simon D. Hoyle; Patrick D. Lynch; Caren Barceló; Jonathan Deroba; Nicholas D. Ducharme‐Barth; Alistair Dunn; Dan Fu; Francisco Izquierdo; Craig Marsh; Haikun Xu; et al. (Fish and Fisheries, 2024)
Spatial models enable understanding potential redistribution of marine resources associated with ecosystem drivers and climate change. Stock assessment platforms can incorporate spatial processes, but have not been widely implemented or simulation tested. To address this research gap, an international simulation experiment was organized. The study design was blinded to replicate uncertainty similar to a real‐world stock assessment process, and a data‐conditioned, high‐resolution operating model (OM) was used to emulate the spatial dynamics and data for Indian Ocean yellowfin tuna ( Thunnus albacares ). Six analyst groups developed both single‐region and spatial stock assessment models using an assessment platform of their choice, and then applied each model to the simulated data. Results indicated that across all spatial structures and platforms, assessments were able to adequately recreate the population trends from the OM. Additionally, spatial models were able to estimate regional population trends that generally reflected the true dynamics from the OM, particularly for the regions with higher biomass and fishing pressure. However, a consistent population biomass scaling pattern emerged, where spatial models estimated higher population scale than single‐region models within a given assessment platform. Balancing parsimony and complexity trade‐offs were difficult, but adequate complexity in spatial parametrizations (e.g., allowing time‐ and age‐variation in movement and appropriate tag mixing periods) was critical to model performance. We recommend expanded use of high‐resolution OMs and blinded studies, given their ability to portray realistic performance of assessment models. Moreover, increased support for international simulation experiments is warranted to facilitate dissemination of methodology across organizations.

Grafting modification of thin-film composite membrane with quaternary ammonium polyelectrolyte for Mg2+/Li+ separation - Xiaomin Ren; Yingying Chen; Yu Wang; Hongyan Fu; Dan Hu; Xudong Feng (Journal of Environmental Chemical Engineering, 2024)

Novel material to enhance the integrity of CCUS cement sheath: Exploration and application of calcium aluminate cement - Peng Gong; Huacai Fu; Dan He; Yuanpeng Wu; Kaiyuan Mei; Chunmei Zhang; Xin He; Tao Liu; Shangdong Li; Xiaowei Cheng (Gas Science and Engineering, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Enhancement of catalytic detoxification of polycyclic aromatic hydrocarbons in fly ash from municipal solid waste incineration via magnetic hydroxyapatite-assisted hydrothermal treatment - Dezhi Shi; Jiayu Liu; Haihang Tong; Kun Fu; Muhammad Salam; Jie Huang; Shuo Xu; Xianyi Wen; Hui Xie; Pan Wang; Huayi Cai; Dan Luo (Science of The Total Environment, 2024)

Appropriate stoichiometric ratios of dissolved organic carbon and nitrate can trigger a transition in nitrate removal in groundwater around plateau lakes, Southwest China - Rongyang Cui; Anqiang Chen; Wanli Hu; Bin Fu; Gangcai Liu; Dan Zhang (Science of The Total Environment, 2024)

Increased precipitation alters the effects of nitrogen deposition on soil bacterial and fungal communities in a temperate forest - Yang Liu; Hang Wang; Xiangping Tan; Shenglei Fu; Dan Liu; Weijun Shen (Science of The Total Environment, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Mapping the profiles and underlying driving mechanisms of the antibiotic resistome and microbiome within a subtropical complex river watershed - Xin-Yuan Zhou; Shu-Yi-Dan Zhou; Fu-Yi Huang; Longji Zhu; Jian-Qiang Su (Journal of Hazardous Materials, 2024)

Complementary imaging of nanoclusters interacting with mitochondria via stimulated emission depletion and scanning transmission electron microscopy - Dan Zhao; Lu Gao; Xiaoyu Huang; Gang Chen; Beibei Gao; Jing Wang; Min Gu; Fu Wang (Journal of Hazardous Materials, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Propyl gallate exposure affects the mouse 2-cell stage embryonic development through inducing oxidative stress and autophagy - Sheng-Ji Yang; Fu-Yi Yang; Yi-Nuo Zou; Yong-Sheng Wang; Zhi-Ming Ding; Li-Dan Zhang; Xu Zhou; Ming Liu; Ze-Qun Duan; Li-Jun Huo (Food and Chemical Toxicology, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

The level of CmFRQ is associated with the degeneration and rejuvenation of Cordyceps militaris fruiting body - Ming-Jia Fu; Dan-Dan Zhang; Jing-Mei Peng; Lei Feng; Zi-Hai Yang; Zi-Yan Huang (Biologia, 2024)

Visualizing the intracellular aggregation behavior of gold nanoclusters via structured illumination microscopy and scanning transmission electron microscopy - Dan Zhao; Jing Wang; Lu Gao; Xiaoyu Huang; Fengping Zhu; Fu Wang (Science of The Total Environment, 2024)

Dispersion of sandy sediments during marine–continental transition: An integrated study from the Late Paleozoic western Ordos Basin - Zhiwei Wang; Lei Liu; Jianling Hu; Feng Wang; Dan Li; Jingqi Zhang; Shuyue Zhu; Rui Zhang; Fei Zhao; Chenggong Zhang; Siyi Fu; Hongde Chen (Marine and Petroleum Geology, 2024)

Long-term seawall barriers lead to the formation of an urban coastal lagoon with increased antibiotic resistome - Shu-Yi-Dan Zhou; Kai Yang; Roy Neilson; Hu Li; Hong-Zhe Li; Yan-Yan Zhou; Juxiu Liu; Jian-Qiang Su; Fu-Yi Huang (Journal of Environmental Management, 2024)

Corrigendum to “Procyanidin B2: A promising multi-functional food-derived pigment for human diseases” [Food Chem. 420 (2023) 136101] - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Synthesis and cytotoxic activity of ethyl ferulate derivatives as potent anti-inflammatory agents - Dan-ni Fu; Zi-yi Kong; Wen Sun; Chun-mei Bai; Yun Wu; Ming Bian; Qian-qian Ma (Natural Product Research, 2024)

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

The characteristic of compound drought and saltwater intrusion events in the several major river estuaries worldwide - Dan Li; Bingjun Liu; Yang Lu; Jianyu Fu (Journal of Environmental Management, 2024)

Development of MoS2-stainless steel catalyst by 3D printing for efficient destruction of organics via peroxymonosulfate activation - Yufeng Liu; Jianhui Xu; Xin Fu; Pengxu Wang; Dan Li; Yunfei Zhang; Shenggui Chen; Chunhui Zhang; Peng Liu (Journal of Environmental Sciences, 2024)

Combined pollution and soil microbial effect of pesticides and microplastics in greenhouse soil of suburban Tianjin, Northern China - Furong Fu; Yang Sun; Dan Yang; Lixia Zhao; Xiaojing Li; Liping Weng; Yongtao Li (Environmental Pollution, 2024)

Surimi freshness monitoring of 4D printing material with anthocyanin - Jun-qi Zhan; Jing-jing Fu; Dan-li Jin; Yan-wei Yuan; Shi-ke Shen; Gao-shang Li; Yue-wen Chen (Journal of Food Engineering, 2023)

Improving the flavor of tilapia fish head soup by adding lipid oxidation products and cysteine - Huixian Fu; Qiaohui Feng; Dan Qiu; Xuanri Shen; Chuan Li; Yanfu He; Wenting Shang (Food Chemistry, 2023)

Transcriptomic and metabonomic to evaluate the effect mechanisms of the growth and aroma-producing of Pichia anomala under ethanol stress - Yanru Chen; Yin Wan; Wenqin Cai; Xiaming Che; Xuehui Sun; Hong Peng; Huibo Luo; Dan Huang; Guiming Fu (Food Bioscience, 2023)

Andrographolide inhibits the activation of spinal microglia and ameliorates mechanical allodynia - Dan Wang; Yongjian Zheng; Junjing Xie; Wenwen Yu; Zhongteng Lu; Wenping Zhang; Yanling Hu; Jianyuan Fu; Qing Sheng; Zhengbing Lv (Metabolic Brain Disease, 2023)

Distinct patterns of the soil and phyllosphere antibiotic resistome in natural forest ecosystems under an altitudinal gradient - Shu-Yi-Dan Zhou; Fu-Yi Huang; Wei Su; Zhiyang Lie; Yue Liu; Chenshuo Lin; Kai Yang; Ze Meng; Zhanfeng Liu; Roy Neilson; Jian-Qiang Su; Juxiu Liu (Science of The Total Environment, 2023)

Simulation of runoff process based on the 3-D river network - Yuan Xue; Chao Qin; Baosheng Wu; Ga Zhang; Xudong Fu; Hongbo Ma; Dan Li; Bingjie Wang (Journal of Hydrology, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

The strength characteristics and competitive failure mechanism of primary coal-rock combination considering interface damage quantity - Kai Wang; Qiang Fu; Chao Xu; Zibo Ai; Dan Li; Longyong Shu (Fuel, 2023)

Revealing the chemical differences and their application in the storage year prediction of Qingzhuan tea by SWATH-MS based metabolomics analysis - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Dan Zou; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Saturation-tolerant prescribed function-based adaptive fault-tolerant tracking control for ACV with uncertainty and faults - Fu Mingyu; Bai Dan; Deng Hanbo; Huang Sunan (Ocean Engineering, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Coloration of cotton fibers with inorganic pigments using a transient high-temperature technology - Qimeng Zhu; Zhuan Fu; Liangjun Xia; Xiaofeng Wang; Zhaozixuan Zhou; Dan Sheng; Xinjie Wei; Junyao Gong; Sijie Zhou; Wenbin Li; Chunhua Zhang (Journal of Cleaner Production, 2023)

Interfacial polymerization process based on diffusion control: Role of chemical composition and morphology on fouling resistance - Xiaomin Ren; Lingxuan Wang; Hongyan Fu; Yu Wang; Dan Hu; Xudong Feng (Journal of Environmental Chemical Engineering, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Two-point-one-line modularized strategy combined with Holliday-junction button probes for multiloci SNPs long-range distribution analysis - Wang Luo; You Wu; Xueping Chen; Li Zhang; Li Wang; Dan Bai; Qian Liu; Ting Wang; Hongyan Yu; Yaxing Xie; Yixin Fu; Zhongzhong Wang; et al. (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Assessing the impact of growth on estimates of fishing mortality — An illustration with Indian Ocean bigeye tuna - Dan Fu; Paul DeBruyn; Fabio Fiorellato; Lauren Nelson; Lucia Pierre; Cynthia FernandezDiaz; Emmanuel Chassot (Regional Studies in Marine Science, 2023)

Procyanidin B2: A promising multi-functional food-derived pigment for human diseases - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2023)

3-D transient electromagnetic inversion based on explicit finite-difference forward modeling - Fei Li; Qiang Tan; Lai-Fu Wen; Dan Huang (Applied Geophysics, 2023)

Current advances in the anti-inflammatory effects and mechanisms of natural polysaccharides - Dan Yuan; Chao Li; Qiang Huang; Xiong Fu; Hao Dong (Critical Reviews in Food Science and Nutrition, 2023)

NIR responsive composite nanomaterials with in-situ deposition of cascaded nanozymes for multiple synergistic therapy of bacterial infection in diabetic mice - Yan Zhang; Chunping Wen; Yijun Liu; Anqi Li; Qiuyan Guo; Xuan Zhang; Li Fu; Shan Xu; Dan Qiao; Pengwu Zheng; Wufu Zhu; Qingshan Pan (Chemical Engineering Journal, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

Validation of the detected Dry–Wet Abrupt Alternation by developing a weighting analysis method - Jianyu Fu; Bingjun Liu; Yang Lu; Manlin Liang; Xuejin Tan; Dan Li; Zeqin Huang (International Journal of Climatology, 2023)
The phenomenon of sudden drought after pluvial (or heavy pluvial after drought) is known as the Dry–Wet Abrupt Alternation (DWAA). This kind of disaster has been evaluated globally based on various DWAA indices. However, few validations have been performed to compare the various DWAA indices. Given that directly validating the identified DWAA events remains difficult because of the limited historical records of DWAA events, in this study, we developed a simple weighting analysis method to cross‐validate the detected DWAA events using three widely‐used indices. The weighting analysis method can be used to estimate the effectiveness of the DWAA indices by calculating the ratio of the synchronous DWAA events (the DWAA events could be synchronously detected by different indices) to the total number of the detected DWAA events. Results suggest that the standard weighted average of precipitation (SWAP) index has better performance for detecting DWAA events in the Pearl River Basin (PRB) compared to other indices. The soil moisture synchronization, meteorological concentration and real DWAA records further testify that the SWAP is more capable of detecting the DWAA events in the PRB. Based on the validation, the SWAP‐derived DWAA events show that both dry–wet (D–W) events and wet–dry events are severe in the upstream sub‐basins in the PRB, while D–W events are more frequent in the downstream PRB. Our study provides a simple but effective method to validate the detected DWAA. The finding underscores the need to validate DWAA detection generated from multiple indicators before further research, and it could help develop adaptation strategies to improve resilience to combined extremes under changing climate.

RETRACTED: Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Properties and potential application of ozone-oxidized starch for enhanced reverse flotation of fine hematite - Ming Zhang; Zeping Xu; Qin Zhang; Zusu Dan; Hongqi Fu; Wei Yao (Minerals Engineering, 2023)

Identify nitrogen transport paths and sources contribution in karst valley depression area using isotopic approach - Meng Lu; Fu-Jun Yue; Xiao-Dan Wang; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Journal of Environmental Management, 2023)

Intestinal microenvironment-mediated allergic dynamic phenotypes and endotypes in the development of gluten allergy - Qiang Xie; Chenglong Liu; Wenhui Fu; Chen Chen; Shimin Gu; Dan Luo; Wentong Xue (Food Research International, 2023)

Highly sensitive and durable MXene/SBS nanofiber-based multifunctional sensors via thiol-ene click chemistry - Yixiang Chen; Xueli Fu; Yu Jiang; Wanqi Feng; Dan Yu; Wei Wang (Chemical Engineering Journal, 2023)

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

Laser-induced microtextured stators coupling with flexible rotors for low-voltage driving rotational piezoelectric motors - Yanhu Zhang; Xuefei Duan; Ji Zhou; Hao Fu; Xiankai Meng; Bao Liu; Jinghu Ji; Xijun Hua; Yonghong Fu; Dan Luo (Chemical Engineering Journal, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

miR ‐124 mediates the expression of ccBax to regulate Cyprinid herpesvirus 2 ( CyHV ‐2)‐induced apoptosis and viral replication - Yan Fu; Junzhe Zhang; Wenjie Cheng; Xingyu Cheng; Liqun Lu; Lang Gui; Yousheng Jiang; Ye Zhang; Dan Xu (Journal of Fish Diseases, 2023)
Cyprinid herpesvirus 2 (CyHV‐2), the etiological agent of herpesvirus haematopoietic necrosis (HVHN) in carp and goldfish, has caused significant economic losses in the aquaculture industry. During viral infection, the host initiates a series of active or passive defences to regulate the process of virus infection. Apoptosis is a key component of active cellular defence, and members of the Bcl‐2 family have been shown to play a critical role in the apoptotic process. However, the mechanism of action of the Bcl‐2 family in inducing apoptosis during CyHV‐2 infection remains unclear. In this study, we revealed the molecular mechanism of miRNA‐mediated silver crucian carp BAX (ccBax) in CyHV‐2‐induced apoptosis for the first time and demonstrated that the overexpression of miR‐124 suppressed ccBax expression and significantly down‐regulated apoptosis in caudal fin cells of Carassius auratus gibelio (GiCF), while miR‐124 inhibitors were the opposite. These studies indicated that miR‐124 inhibits CyHV‐2‐induced apoptosis by reducing the expression of ccBax. Furthermore, the fact that transfection of miR‐124 mimics promoted CyHV‐2 replication, whereas miR‐124 inhibitors inhibited CyHV‐2 replication, indicated that miR‐124 inhibited CyHV‐2‐induced apoptosis and contributed to viral replication. All these results suggested that miR‐124 suppresses virus‐induced apoptosis and promotes viral replication by targeting and regulating ccBax expression.

Long‐term variability in the fish assemblage around Japan over the last century and early warning signals of regime shifts - Yongjun Tian; Caihong Fu; Akihiko Yatsu; Yoshiro Watanabe; Yang Liu; Jianchao Li; Dan Liu; Yumeng Pang; Jiahua Cheng; Ching‐Hsein Ho; Shuyang Ma (Fish and Fisheries, 2023)
The marine ecosystems around Japan are very productive and have typical wasp‐waist structure dominated by small pelagic fishes such as sardine, exhibiting large low‐frequency fluctuations in biomass. Whereas studies on the variability in abundance of individual species such as sardine and anchovy are popular, only a few studies focused on the long‐term variability of fish assemblage around Japan. In this study, 13 species/taxa ranging from small forage to large predatory species and from warm‐ to cold‐water species were selected to indicate essential characteristics of the fish assemblage and their drivers were analysed based on fishery, oceanographic and climatic data sets from 1901 to 2018. Results show that two outstanding peaks during the 1930s and 1980s were characterized by abundant sardine. Additionally, species composition showed high similarities during similar temperature regimes while exhibiting contrasts during different temperature regimes. Variations and regime shifts in dominant patterns and fish community indices coincided well with the Atlantic Multidecadal Oscillation (AMO) and regional sea surface temperature (SST). Furthermore, gradient forest analysis identified AMO and regional SSTs as most important predictors of dominant patterns and fish community indices, suggesting that the decadal and multidecadal variability in the fish assemblage around Japan was forced by basin‐scale climate variability as inherent in the AMO through its connections with regional SSTs. Autocorrelation coefficient demonstrated that the ecological indicators have the potential to be early warning signals of regime shifts, which suggests the possibility of coming cold regime since around 2015 and has important implications for fisheries management.

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Evaluation of modified bitumen properties using waste plastic pyrolysis wax as warm mix additives - Chuanqiang Li; Haobo Wang; Chaoliang Fu; Shaosong Shi; Guannan Li; Qizheng Liu; Dan Zhou; Lin Jiang; Ying Cheng (Journal of Cleaner Production, 2023)

Electrochemical activation of peroxymonosulfate by 3D printed blue TiO2 nanotube arrays reactive electrochemical membrane for efficient degradation of acetaminophen - Jianhui Xu; Yufeng Liu; Dan Li; Chunhui Zhang; Xin Fu; Yunfei Zhang; Pengxu Wang; Jincheng Lu; Shenggui Chen; Lei Li (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

A systematical review on ethnobotanical, phytochemical and pharmacological aspects of Dendrobium nobile Lindl. - Qian Zhang; Xiujuan Fu; Hao Liu; Yangxi Chen; Siwei Chen; Hong Niu; Yu Luo; Hui Lei; Dan Zhang (Phytochemistry Reviews, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

CRISPR/Cas9-mediated targeted mutagenesis of two homoeoalleles in tobacco confers resistance to powdery mildew - Wang Xuebo; Li Dandan; Tan Xiaolei; Cai Changchun; Zhang Xinyao; Shen Zhan; Yang Aiguo; Fu Xiankui; Liu Dan (Euphytica, 2023)

Face it and shoulder it jointly: from personal experience to mitigation behavior of climate change - Yuling Fu; Jiaxin Shi; Dan Su; Fumin Deng (Environment, Development and Sustainability, 2023)

Global ocean reanalysis CORA2 and its inter comparison with a set of other reanalysis products - Hongli Fu; Bo Dan; Zhigang Gao; Xinrong Wu; Guofang Chao; Lianxin Zhang; Yinquan Zhang; Kexiu Liu; Xiaoshuang Zhang; Wei Li (Frontiers in Marine Science, 2023)
We present the China Ocean ReAnalysis version 2 (CORA2) in this paper. We compare CORA2 with its predecessor, CORA1, and with other ocean reanalysis products created between 2004 and 2019 [GLORYS12v1 (Global Ocean reanalysis and Simulation), HYCOM (HYbrid Coordinate Ocean Model), GREP (Global ocean Reanalysis Ensemble Product), SODA3 (Simple Ocean Data Assimilation, version 3), and ECCO4 (Estimating the Circulation and Climate of the Ocean, version 4)], to demonstrate its improvements and reliability. In addition to providing tide and sea ice signals, the accuracy and eddy kinetic energy (EKE) of CORA2 are also improved owing to an enhanced resolution of 9 km and updated data assimilation scheme compared with CORA1. Error analysis shows that the root-mean-square error (RMSE) of CORA2 sea-surface temperature (SST) remains around 0.3°C, which is comparable to that of GREP and smaller than those of the other products studied. The subsurface temperature (salinity) RMSE of CORA2, at 0.87°C (0.15 psu), is comparable to that of SODA3, smaller than that of ECCO4, and larger than those of GLORYS12v1, HYCOM, and GREP. CORA2 and GLORYS12v1 can better represent sub-monthly-scale variations in subsurface temperature and salinity than the other products. Although the correlation coefficient of sea-level anomaly (SLA) in CORA2 does not exceed 0.8 in the whole region, as those of GREP and GLORYS12v1 do, it is more effective than ECCO4 and SODA3 in the Indian Ocean and Pacific Ocean. CORA2 can reproduce the variations in steric sea level and ocean heat content (OHC) on the multiple timescales as the other products. The linear trend of the steric sea level of CORA2 is closer to that of GREP than that of the other products, and the long-term warming trends of global OHC in the high-resolution CORA2 and GLORYS12v1 are greater than those in the low-resolution EN4 and GREP. Although CORA2 shows overall poorer performance in the Atlantic Ocean, it still achieves good results from 2009 onward. We plan to further improve CORA2 by assimilating the best available observation data using the incremental analysis update (IAU) procedure and improving the SLA assimilation method.

Revealing the potential of organo-mineral complexes in agricultural application using bibliometrics - Xuehao Zheng; Belay Tafa Oba; Han Wang; Bin Zhang; Chengqiang Shu; Yan Song; Jianfeng Fu; Shejiang Liu; Yuxin Zhang; Nan Dai; Dan Song; Hui Ding (Journal of Cleaner Production, 2023)

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Viscosity-triggered near-infrared fluorescence nanoprobe for in vivo non-invasive diagnosis of cancer - Wen-Juan Fu; Jian Ting Li; Wen Hui Qian; Xiang Ying Zhang; Dan Dan Ma; Yu Ting Wang; Qi Jia Zhang; Dong Zhu (Chemical Engineering Journal, 2023)

High-strength and recyclable pure chitosan films manufactured by an ionic liquid assisted roll-forming method - Shuang Sun; Jiaqi Zheng; Zijie Liu; Siluo Huang; Qikuan Cheng; Yue Fu; Weihao Cai; Dan Chen; Dong Wang; Huamin Zhou; Yunming Wang (Chemical Engineering Journal, 2023)

TMT-based quantitative proteomics analysis reveals the differential proteins between fresh and frozen-thawed sperm of yak (Bos grunniens) - Yilin Fan; Xiaowei Li; Yu Guo; Xiaoqiang He; Yanwen Wang; Dan Zhao; Yan Ma; Xinxin Feng; Jiyue Zhang; Jian Li; Xiangdong Zi; Xianrong Xiong; et al. (Theriogenology, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

A parsimonious model for predicting the NO3−-N concentration in shallow groundwater in intensive agricultural areas using few easily accessible indicators and small datasets based on machine learning - Panlei Wang; Dan Zhang; Xiang Tao; Wanli Hu; Bin Fu; Hui Yan; Yanhua Pan; Anqiang Chen (Journal of Hydrology, 2023)

Loss of SUN1 function in spermatocytes disrupts the attachment of telomeres to the nuclear envelope and contributes to non-obstructive azoospermia in humans - Qingxia Meng; Binbin Shao; Dan Zhao; Xu Fu; Jiaxiong Wang; Hong Li; Qiao Zhou; Tingting Gao (Human Genetics, 2023)

Shifts in the sources and fates of nitrate in shallow groundwater caused by agricultural intensification intensity: Revealed by hydrochemistry, stable isotopic composition and source contribution - Rongyang Cui; Dan Zhang; Hongyuan Wang; Bin Fu; Hui Yan; Wanli Hu; Gangcai Liu; Anqiang Chen (Agriculture, Ecosystems & Environment, 2023)

Analysis of coniferous tree growth gradients in relation to regional pollution and climate change in the Miyun Reservoir Basin, China - Li Fu; Yan Xu; Dan Zhao; Bingfang Wu; Zhihong Xu (Environmental Science and Pollution Research, 2023)
Forests play a crucial role in regulating regional climate and mitigating local air pollution, but little is known about their responding to such changes. This study aimed to examine the potential responses of Pinus tabuliformis , the major coniferous tree species in the Miyun Reservoir Basin (MRB), along an air pollution gradient in Beijing. Tree rings were collected along a transect, and ring width (basal area increment, BAI) and chemical characteristics were determined and related to long-term climatic and environmental records. The results showed that Pinus tabuliformis showed an overall increase in intrinsic water-use efficiency ( iWUE ) at all sites, but the relationships between iWUE and BAI differed among the sites. The contribution of atmospheric CO 2 concentration ( c a ) to tree growth was significant at the remote sites (> 90%). The study found that air pollution at these sites might have caused further stomatal closure, as evidenced by the higher δ 13 C levels (0.5 to 1‰ higher) during heavy pollution periods. The analysis of tree ring δ 15 N also revealed the potential of using δ 15 N to fingerprint major nitrogen (N) deposition, as shown in the increasing tree ring δ 15 N, and major nitrogen losses due to denitrification and leaching, as shown in the higher δ 15 N in tree rings during heavy rainfall events. Overall, the gradient analysis indicated the contributions of increasing c a , increasing water deficit and elevated air pollution to tree growth and forest development. The different BAI trajectories suggested that Pinus tabuliformis has the ability to adapt to the harsh environment in the MRB.

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Risk assessment of Artemia egg shell-Mg-P composites as a slow-release phosphorus fertilizer during its formation and application in typical heavy metals contaminated environment - Sufeng Wang; Xiaojuan Lv; Mingwei Fu; Zijing Wang; Dan Zhang; Qina Sun (Journal of Environmental Management, 2023)

Failure mechanism and movement process of three loess landslides due to freeze-thaw cycle in the Fangtai village, Yongjing County, Chinese Loess Plateau - Jiaxu Kong; Jianqi Zhuang; Jianbing Peng; Penghui Ma; Jiewei Zhan; Jiaqi Mu; Jie Wang; Dan Zhang; Jia Zheng; Yuting Fu; Shibao Wang; Chenhui Du (Engineering Geology, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Highly oxygenated diterpenoids in Clerodendranthus spicatus and their bioactivity, A review - Yaqi Zhang; Yang Fu; Jingya Ruan; Qian Gao; Dingshan Yang; Dan Wang; Yi Zhang; Tao Wang (Biochemical Systematics and Ecology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

A modified inherent thermal runaway hazard index (m-ITHI) for risk assessment of chemical processes based on cloud model - Feifei Chen; Dan Wei; Lei Ni; Juncheng Jiang; Gang Fu (Process Safety and Environmental Protection, 2023)

Impacts of climate change on future hurricane induced rainfall and flooding in a coastal watershed: A case study on Hurricane Harvey - Xudong Li; Dan Fu; John Nielsen-Gammon; Sudershan Gangrade; Shih-Chieh Kao; Ping Chang; Mario Morales Hernández; Nathalie Voisin; Zhe Zhang; Huilin Gao (Journal of Hydrology, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Increasing clinician participation in tobacco cessation by an implementation science-based tobacco cessation champion program - Cary A. Presant; Kimlin Ashing; Sophia Yeung; Jonjon Macalintal; Brian Tiep; Argelia Sandoval; Susan Brown; Mary Cianfrocca; Loretta Erhunmwunsee; Dan Raz; Arya Amini; Ravi Salgia; et al. (Cancer Causes & Control, 2023)

Effects of the probability of pulse-like ground motions on landslide susceptibility assessment in near-fault areas - Jing Liu; Hai-ying Fu; Ying-bin Zhang; Pei-yi Xu; Run-dan Hao; Hai-hong Yu; Yun-yong He; Hong-yan Deng; Lu Zheng (Journal of Mountain Science, 2023)

The Joint Anaerobic Denitrification Performance of Klebsiella sp. and Enterobacter hormaechei Using Two Carbon Substrates With and Without the Presence of Heavy Metals - George Kwame Amoako-Nimako; Fangmin Chen; Jingjing Fu; Dan Yu; Xinyao Yang (Water, Air, & Soil Pollution, 2022)

The effect of reservoir expansion from underground karst cave to surface reservoir on water quality in southwestern China - Meng Lu; Xiao-Dan Wang; Fu-Jun Yue; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Environmental Science and Pollution Research, 2022)

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Goethite and lepidocrocite catalyzing different double-oxidant systems to degrade chlorophenol - Dan Zhong; Weinan Feng; Wencheng Ma; Xinyue Liu; Jun Ma; Ziyi Zhou; Xuan Du; Fu He (Environmental Science and Pollution Research, 2022)

Relative reinforcing effects of dibutylone, ethylone, and N-ethylpentylone: self-administration and behavioral economics analysis in rats - Miaojun Lai; Dan Fu; Zeming Xu; Han Du; Huifen Liu; Youmei Wang; Peng Xu; Wenhua Zhou (Psychopharmacology, 2022)

Life cycle assessment of auto-tropically cultivated economic microalgae for final products such as food, total fatty acids, and bio-oil - Dan Zhang; Siyuan An; Rao Yao; Wen Fu; Yujie Han; Ming Du; Zixi Chen; Anping Lei; Jiangxin Wang (Frontiers in Marine Science, 2022)
Life cycle assessment (LCA) is a powerful tool to evaluate environmentally sustainable production or consumption of various goods or services. Microalgae are single-celled green factories and good resources of biofuels, bioactive products, food ingredients, and degradable biomaterials. Currently, microalgae are also valuable for mitigating elevated greenhouse gases like CO 2 levels and treatment of wastewater. LCA evaluation was limited and separated, majorly in microalgal biofuels and heterotrophic cultivation. Comparative LCA for different final algal products such as algal powder, bio-oil, total fatty acid, and residue recycling is still limited, especially autotrophic algal cultivation for products other than bio-oils and biofuels. Thus, we chose several autotrophic cultivated microalgae and made a comparative LCA among these selected species and a detailed step-by-step production in Chlorella sp. Results indicated that we could significantly reduce the production cost and lower environmental impacts by selecting algal species and final products, optimizing methods for algal cultivation, biomass separation, and drying process, and land selection plus electricity renewable energy, together with thermal power plants nearby for CO 2 or flu gas. It shed light on the insight of microalgal consumption selection under current international requirements and challenges for carbon sequestration.

An innovative material for simultaneous removal of phosphorus and ammonia nitrogen in river water: Preparation and application - Xinyan Wei; Xiaori Fu; Zhikang Zhou; Wei Zhang; Dan Qian; Guilu Zeng; Shuguang Lyu (Water, Air, & Soil Pollution, 2022)

Non-peer-reviewed data, effect measures, and meta-regression analysis on proton pump inhibitor use and COVID-19 - Dan-Na Wu; Li-Rong Jiao; Guo-Fu Li; Guo Yu (European Journal of Clinical Pharmacology, 2022)

Circular RNA circPBX3 promotes cisplatin resistance of ovarian cancer cells via interacting with IGF2BP2 to stabilize ATP7A mRNA expression - Lihua Fu; Dan Zhang; Nuo Yi; Yanjun Cao; Yaxian Wei; Wenjing Wang; Li Li (Human Cell, 2022)

Differential ubiquitome analysis of Cordyceps militaris lysine-ubiquitinated proteins affected by blue light - Zi-Yan Huang; Lei Feng; Ming-Jia Fu; Dan-Dan Zhang (Biologia, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

microRNA (miR‐KT‐635) encoded by Cyprinid herpesvirus 2 regulates the viral replication with targeting to the ORF23 - Qikang Chen; Yang Luo; Yan Fu; Zizhao Feng; Liqun Lu; Yousheng Jiang; Dan Xu (Journal of Fish Diseases, 2022)
Herpesviruses have been reported to be able to encode and express functional viral microRNAs that target both viral and cellular transcripts. In our previous studies, we found a new miRNA miR‐KT‐635 encoded by Cyprinid herpesvirus 2, which is predicted to target viral genes and cellular genes involved in innate immune signalling pathway and apoptosis. However, the function and target gene of miR‐KT‐635 are not proved. In this study, the regulating target gene of miR‐KT‐635 was proved as the viral gene ORF23 directly, the target point sequence on gene was verified and miR‐KT‐635 was identified to regulate the expression of ORF23 protein. According to the bioinformatics analysis, the tRNA domain and ribosome domain in the protein sequence of ORF23 were found to share high homology with R2i and P53R2i, which are related to the ribonucleotide reductase small subunit in the host (transform NTP to dNTP). Within expectations, silencing of viral ORF23 or transfecting miR‐KT‐635 mimics in Carassius auratus gibelio caudal fin cell line (GiCF) could suppress viral propagation significantly.

Water Resources Liability Measurement and the Driving Factors of Water Resources Liability Intensity - Dan-dan Zhang; Ju-qin Shen; Fu-hua Sun (Water Resources Management, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Field investigation and numerical simulation on rockfalls in Zhangmu Town, Tibet, China - Zhong-fu Wang; Han-dong Liu; Si-ming He; Dan Bi (Journal of Mountain Science, 2022)

Using data-limited approaches to assess data-rich Indian Ocean bigeye tuna: Data quantity evaluation and critical information for management implications - Ya’nan Li; Jiangfeng Zhu; Xiaojie Dai; Dan Fu; Yong Chen (Acta Oceanologica Sinica, 2022)

Phactr1 negatively regulates bone mass by inhibiting osteogenesis and promoting adipogenesis of BMSCs via RhoA/ROCK2 - Wei Lin; Zhipeng Chen; Xiaoyi Mo; Shengli Zhao; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Journal of Molecular Histology, 2022)

Uncoupling protein 1 knockout aggravates isoproterenol-induced acute myocardial ischemia via AMPK/mTOR/PPARα pathways in rats - Daorong Hou; Heling Fu; Yuan Zheng; Dan Lu; Yuanwu Ma; Yuan Yin; Lianfeng Zhang; Dan Bao (Transgenic Research, 2022)
Uncoupling protein 1 (UCP1) was found exclusively in the inner membranes of the mitochondria of brown adipose tissue (BAT). We found that UCP1 was also expressed in heart tissue and significantly upregulated in isoproterenol (ISO)-induced acute myocardial ischemia (AMI) rat model. The present study is to determine the underlying mechanism involved in the UCP1 upregulation in ISO-induced AMI rat model. The Ucp1 −/− rats were generated by CRISPR-Cas9 system and presented decreased BAT volume. 2-months old Sprague Dawley (SD) wild-type (WT) and Ucp1 −/− rats were treated with ISO intraperitoneally 30 mg/kg once a day for 3 consecutive days to establish AMI model. In saline group, the echocardiographic parameters, serum markers of myocardial injury cardiac troponin I (cTnI), creatine kinase isoenzyme MB (CK-MB), oxidant malondialdehyde (MDA), antioxidant superoxide dismutase (SOD) or fibrosis were comparable between WT and Ucp1 −/− rats. ISO treatment induced worse left ventricle (LV) hypertrophy, myocardial fibrosis, increased higher cTnI, CK-MB and MDA and decreased lower SOD level in Ucp1 −/− rats compared with that of WT rats. Ucp1 −/− rats also presented lower myocardial phosphocreatine (PCr)/ATP-ratio, which demonstrated worse cardiac energy regulation defect. ISO treatment induced the phosphorylation of AMP-activated protein kinase (AMPK) activation, subsequently the phosphorylation of mammalian target of rapamycin (mTOR) inhibition and peroxisome proliferators-activated receptor α (PPARα) activation in WT rats, whereas activation of AMPK/mTOR/PPARα pathways significantly inhibited in Ucp1 −/− rats. To sum up, UCP1 knockout aggravated ISO-induced AMI by inhibiting AMPK/mTOR/PPARα pathways in rats. Increasing UCP1 expression in heart tissue may be a cytoprotective therapeutic strategy for AMI.

Improved tree-based machine learning algorithms combining with bagging strategy for landslide susceptibility modeling - Tingyu Zhang; Renata Pacheco Quevedo; Huanyuan Wang; Quan Fu; Dan Luo; Tao Wang; Guilherme Garcia de Oliveira; Laurindo Antonio Guasselli; Camilo Daleles Renno (Arabian Journal of Geosciences, 2022)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

miR-106b-5p upregulation is associated with microglial activation and inflammation in the mouse hippocampus following status epilepticus - Tao Yu; Hui Fu; Jing-Jing Sun; Dan-Rui Ding; Hua Wang (Experimental Brain Research, 2021)

Dynamics of antibiotic resistance and its association with bacterial community in a drinking water treatment plant and the residential area - Fu-Yi Huang; Qing-Lin Chen; Xian Zhang; Roy Neilson; Jian-Qiang Su; Shu-Yi-Dan Zhou (Environmental Science and Pollution Research, 2021)

Critical transitions and ecological resilience of large marine ecosystems in the Northwestern Pacific in response to global warming - Shuyang Ma; Dan Liu; Yongjun Tian; Caihong Fu; Jianchao Li; Peilong Ju; Peng Sun; Zhenjiang Ye; Yang Liu; Yoshiro Watanabe (Global Change Biology, 2021)
Natural systems can undergo critical transitions, leading to substantial socioeconomic and ecological outcomes. “Ecological resilience” has been proposed to describe the capacity of natural systems to absorb external perturbation and reorganize while undergoing change so as to still retain essentially the same function, structure, identity, and feedbacks. However, the mere application of ecological resilience in theoretical research and the lack of quantitative approaches present considerable obstacles for predicting critical transitions and understanding their mechanisms. Large marine ecosystems (LMEs) in the Northwestern Pacific are characterized by great biodiversity and productivity, as well as remarkable warming in recent decades. However, no information is available on the critical transitions and ecological resilience of LMEs in response to warming. Therefore, we applied an integrated resilience assessment framework to fisheries catch data from seven LMEs covering a wide range of regions, from tropical to subarctic, in the Northwestern Pacific to identify critical transitions, assess ecological resilience, and reconstruct folded stability landscapes, with a specific focus on the effects of warming. The results provide evidence of the occurrence of critical transitions, with fold bifurcation and hysteresis in response to increasing sea surface temperatures (SSTs) in the seven LMEs. In addition, these LMEs show similarities and synchronies in structure variations and critical transitions forced by warming. Both dramatic increases in SST and small fluctuations at the corresponding thresholds may trigger critical transitions. Ecological resilience decreases when approaching the tipping points and is repainted as the LMEs shift to alternative stable states with different resilient dynamics. Folded stability landscapes indicate that the responses of LMEs to warming are discontinuous, which may be caused by the reorganization of LMEs as their sensitivity to warming changes. Our study clarifies the nonlinear responses of LMEs to anthropogenic warming and provides examples of quantifying ecological resilience in empirical systems at unprecedented spatial and temporal scales.

Role of nucleus accumbens microRNA-181a and MeCP2 in incubation of heroin craving in male rats - Wenjin Xu; Qingxiao Hong; Zi Lin; Hong Ma; Weisheng Chen; Dingding Zhuang; Huaqiang Zhu; Miaojun Lai; Dan Fu; Wenhua Zhou; Huifen Liu (Psychopharmacology, 2021)

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Use of High-Throughput Sequencing to Identify Fungal Communities on the Surface of Citri Reticulatae Pericarpium During the 3-Year Aging Process - Fangqing Yang; Dan Yang; Sujuan Liu; Shuangmei Xu; Fu Wang; Hongping Chen; Youping Liu (Current Microbiology, 2021)

Effects of continuous cucumber cropping on crop quality and soil fungal community - Kaining Sun; Longyun Fu; Yang Song; Liang Yuan; Haoran Zhang; Dan Wen; Ning Yang; Xiao Wang; Yaoquan Yue; Xuhua Li; Kean Wang (Environmental Monitoring and Assessment, 2021)

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Bridge Crack Semantic Segmentation Based on Improved Deeplabv3+ - Huixuan Fu; Dan Meng; Wenhui Li; Yuchao Wang (Journal of Marine Science and Engineering, 2021)
Cracks are the main goal of bridge maintenance and accurate detection of cracks will help ensure their safe use. Aiming at the problem that traditional image processing methods are difficult to accurately detect cracks, deep learning technology was introduced and a crack detection method based on an improved DeepLabv3+ semantic segmentation algorithm was proposed. In the network structure, the densely connected atrous spatial pyramid pooling module was introduced into the DeepLabv3+ network, which enabled the network to obtain denser pixel sampling, thus enhancing the ability of the network to extract detail features. While obtaining a larger receptive field, the number of network parameters was consistent with the original algorithm. The images of bridge cracks under different environmental conditions were collected, and then a concrete bridge crack segmentation data set was established, and the segmentation model was obtained through end-to-end training of the network. The experimental results showed that the improved DeepLabv3+ algorithm had higher crack segmentation accuracy than the original DeepLabv3+ algorithm, with an average intersection ratio reaching 82.37%, and the segmentation of crack details was more accurate, which proved the effectiveness of the proposed algorithm.

Long-Term Variability of Piscivorous Fish in China Seas Under Climate Change With Implication for Fisheries Management - Dan Liu; Yongjun Tian; Shuyang Ma; Jianchao Li; Peng Sun; Zhenjiang Ye; Caihong Fu; Kuowei Lan; Shijie Zhou (Frontiers in Marine Science, 2021)
Due to persistent fishing expansion in the China Seas over the past six decades, fisheries resources have been over-exploited; as a result, exploited fish have become smaller in size and younger in age. Marine piscivorous fish constituted a large portion of Chinese fisheries catch, long-term variability of which has rarely been investigated despite intense fishing pressure and climate change. In this study, we attempt to identify their responses to climate change and fishing activities and to provide scientific basis for sustainable exploitation of these resources. Seven taxa from pelagic to demersal species inhabiting either cold-water or warm-water were selected to represent the piscivorous fish assemblage in the China Seas. Total catch of these piscivorous fish in the China Seas increased during the early 1990s, stabilizing around 1.2 million tons after 1997. Principal component analysis (PCA) showed evident interannual-decadal variabilities in the catch of these fish with step changes around 1985/86 and 1997/98. Individual taxa, however, showed different trends in catches with sharks, rays, and lizardfishes manifesting downward trends while Pacific cod, eels, and hairtail increasing. Common dolphinfish and Japanese-Spanish mackerel increased largely in the 1990s but declined slightly during the 2000s. Although there were temporal overlaps between climate change and fishing variabilities, results of gradient forest analyses indicated that fishing effort imposed the most important influence on piscivorous fish. And among all climate variables explored in this study, sea surface temperature (SST) especially that of the East China Sea, had greatest impacts on variations in piscivorous fish catch, which may have been gradually exacerbated by the continued high fishing intensity. In addition, significant changes were identified in the life history traits in the species we evaluated, such as reduced average body sizes and truncated age compositions, strongly indicating the effect of fishing. We therefore advocate precautionary fishery practices under climate change.

Decoupling analysis of the industrial growth and environmental pollution in the Circum-Bohai-Sea region in China - Yanling Xi; Dan Yan; Jian Zhang; Xiangshan Fu (Environmental Science and Pollution Research, 2021)

Nrf2 deficiency aggravates the kidney injury induced by subacute cadmium exposure in mice - Chengjie Chen; Xue Han; Gang Wang; Dan Liu; Lina Bao; Congcong Jiao; Junjun Luan; Yongyong Hou; Yuanyuan Xu; Huihui Wang; Qiang Zhang; Hua Zhou; et al. (Archives of Toxicology, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Response of palladium in receiving water bodies to rainfall-runoff - Fangfang Ding; Yuyan Liu; Zucheng Wang; Caiye Ji; Dan Wu; Lin Wang; Bo Fu; Lan Zhang; Haofeng Liu (Environmental Science and Pollution Research, 2021)

Correction to: A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2021)

Safety of protease inhibitors and Arbidol for SARS-CoV-2 pneumonia in Zhejiang Province, China - Yong-zheng Guo; Kai-jin Xu; Yong-tao Li; Jia-dan Fu; Min Xu; Ling Yu; Ji-fang Sheng; Biao Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Effects of climate variability and land use/land cover change on the Daihai wetland of central Inner Mongolia over the past decades - Xi Chun; Fu-ying Qin; Hai-jun Zhou; Dan Dan; Ying-ying Xia; Khukhuudei Ulambadrakh (Journal of Mountain Science, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Whole-Brain Map of Long-Range Monosynaptic Inputs to Different Cell Types in the Amygdala of the Mouse - Jia-Yu Fu; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Meng-Yu Tang; Bin Yu; Xiao-Ming Li (Neuroscience Bulletin, 2020)
The amygdala, which is involved in various behaviors and emotions, is reported to connect with the whole brain. However, the long-range inputs of distinct cell types have not yet been defined. Here, we used a retrograde trans-synaptic rabies virus to generate a whole-brain map of inputs to the main cell types in the mouse amygdala. We identified 37 individual regions that projected to neurons expressing vesicular glutamate transporter 2, 78 regions to parvalbumin-expressing neurons, 104 regions to neurons expressing protein kinase C-δ, and 89 regions to somatostatin-expressing neurons. The amygdala received massive projections from the isocortex and striatum. Several nuclei, such as the caudate-putamen and the CA1 field of the hippocampus, exhibited input preferences to different cell types in the amygdala. Notably, we identified several novel input areas, including the substantia innominata and zona incerta. These findings provide anatomical evidence to help understand the precise connections and diverse functions of the amygdala.

Stability Analysis of Unsaturated Slopes Considering Combined Influences of Strength Non-homogeneity and Non-saturation - Dan-ping Gu; Tong-hua Ling; Fu Huang; Liang Zhang (Geotechnical and Geological Engineering, 2020)

Model tests on performance of offshore wind turbine with suction caisson foundation in sand - Hai-lei Kou; Dan-liang Yang; Wang-chun Zhang; Yi-fan Wu; Qiang Fu (Marine Georesources & Geotechnology, 2020)

Trehalose attenuates TGF-β1-induced fibrosis of hSCFs by activating autophagy - Nianxuan Wu; Liangbo Chen; Dan Yan; Meng Zhou; Chunyi Shao; Yang Lu; Qinke Yao; Hao Sun; Yao Fu (Molecular and Cellular Biochemistry, 2020)

The economic loss of health effect damages from PM2.5 pollution in the Central Plains Urban Agglomeration - Xiangshan Fu; Li Li; Yalin Lei; Sanmang Wu; Dan Yan; Ximing Luo; Hui Luo (Environmental Science and Pollution Research, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Nitrogen fertilizer enhances zinc and cadmium uptake by hyperaccumulator Sedum alfredii Hance - Ziwen Lin; Chunying Dou; Yongfu Li; Hailong Wang; Nabeel Khan Niazi; Shaobo Zhang; Dan Liu; Keli Zhao; Weijun Fu; Yongchun Li; Zhengqian Ye (Journal of Soils and Sediments, 2020)

Non-Gaussian Lagrangian Stochastic Model for Wind Field Simulation in the Surface Layer - Chao Liu; Li Fu; Dan Yang; David R. Miller; Junming Wang (Advances in Atmospheric Sciences, 2020)
Wind field simulation in the surface layer is often used to manage natural resources in terms of air quality, gene flow (through pollen drift), and plant disease transmission (spore dispersion). Although Lagrangian stochastic (LS) models describe stochastic wind behaviors, such models assume that wind velocities follow Gaussian distributions. However, measured surface-layer wind velocities show a strong skewness and kurtosis. This paper presents an improved model, a non-Gaussian LS model, which incorporates controllable non-Gaussian random variables to simulate the targeted non-Gaussian velocity distribution with more accurate skewness and kurtosis. Wind velocity statistics generated by the non-Gaussian model are evaluated by using the field data from the Cooperative Atmospheric Surface Exchange Study, October 1999 experimental dataset and comparing the data with statistics from the original Gaussian model. Results show that the non-Gaussian model improves the wind trajectory simulation by stably producing precise skewness and kurtosis in simulated wind velocities without sacrificing other features of the traditional Gaussian LS model, such as the accuracy in the mean and variance of simulated velocities. This improvement also leads to better accuracy in friction velocity (i.e., a coupling of three-dimensional velocities). The model can also accommodate various non-Gaussian wind fields and a wide range of skewness–kurtosis combinations. Moreover, improved skewness and kurtosis in the simulated velocity will result in a significantly different dispersion for wind/particle simulations. Thus, the non-Gaussian model is worth applying to wind field simulation in the surface layer.

Breast milk concentration of hydroxychloroquine in Chinese lactating women with connective tissue diseases - Wenxiu Peng; Rongji Liu; Lejia Zhang; Qiang Fu; Dan Mei; Xiaoli Du (European Journal of Clinical Pharmacology, 2019)

miR-183-5p enhances the radioresistance of colorectal cancer by directly targeting ATG5 - Sheng Zheng; Yong-Fu Zhong; De-Ming Tan; Yue Xu; Huai-Xiang Chen; Dan Wang (Journal of Biosciences, 2019)

Identification of rare variants in cardiac sodium channel β4-subunit gene SCN4B associated with ventricular tachycardia - Qin Yang; Hongbo Xiong; Chengqi Xu; Yuan Huang; Xin Tu; Gang Wu; Fenfen Fu; Zhijie Wang; Longfei Wang; Yuanyuan Zhao; Sisi Li; Yufeng Huang; et al. (Molecular Genetics and Genomics, 2019)

Identification of floral aromatic volatile compounds in 29 cultivars from four groups of Osmanthus fragrans by gas chromatography–mass spectrometry - Jianxin Fu; Dan Hou; Yiguang Wang; Chao Zhang; Zhiyi Bao; Hongbo Zhao; Shaoqing Hu (Horticulture, Environment, and Biotechnology, 2019)

Improved Jayaweera-Mikkelsen model to quantify ammonia volatilization from rice paddy fields in China - Xiaoying Zhan; Chuan Chen; Qihui Wang; Feng Zhou; Kentaro Hayashi; Xiaotang Ju; Shu Kee Lam; Yonghua Wang; Yali Wu; Jin Fu; Luping Zhang; Shuoshuo Gao; et al. (Environmental Science and Pollution Research, 2019)

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

Effect of controlled-release fertilizer on N2O emissions and tea yield from a tea field in subtropical central China - Yanzheng Wu; Yong Li; Xiaoqing Fu; Jianlin Shen; Dan Chen; Yi Wang; Xinliang Liu; Runlin Xiao; Wenxue Wei; Jinshui Wu (Environmental Science and Pollution Research, 2018)

Haploid plant regeneration from hardy kiwifruit (Actinidia arguta Planch.) anther culture - Guang-Fu Wang; Hong-Yan Qin; Dan Sun; Shu-Tian Fan; Yi-Ming Yang; Zhen-Xing Wang; Pei-Llei Xu; Ying Zhao; Ying-Xue Liu; Jun Ai (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Scutellarin suppresses neuroinflammation via the inhibition of the AKT/NF-κB and p38/JNK pathway in LPS-induced BV-2 microglial cells - Pengtao You; San Fu; Kun Yu; Yu Xia; Hezhen Wu; Yanfang Yang; Chaozhi Ma; Dan Liu; Xin Chen; Jun Wang; Xiaochuan Ye; Yanwen Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Plasma miR-124 Is a Promising Candidate Biomarker for Human Intracerebral Hemorrhage Stroke - Zifeng Wang; Gang Lu; Johnny Sze; Yao Liu; Sheng Lin; Hong Yao; Ji Zhang; Dan Xie; Quentin Liu; Hsiang-fu Kung; Marie Chia-mi Lin; Wai Sang Poon (Molecular Neurobiology, 2018)

The role of heat shock protein 70 in oxidant stress and inflammatory injury in quail spleen induced by cold stress - Jiayi Ren; Chunpeng Liu; Dan Zhao; Jing Fu (Environmental Science and Pollution Research, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

Complexity measurement of precipitation series in urban areas based on particle swarm optimized multiscale entropy - Dong Liu; Chen Cheng; Qiang Fu; Yongjia Zhang; Yuxiang Hu; Dan Zhao; Muhammad Imran Khan; Muhammad Abrar Faiz (Arabian Journal of Geosciences, 2018)

A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2018)

Temporal-spatial variations and influencing factors of nitrogen in the shallow groundwater of the nearshore vegetable field of Erhai Lake, China - Anqiang Chen; Baokun Lei; Wanli Hu; Hongyuan Wang; Limei Zhai; Yanting Mao; Bin Fu; Dan Zhang (Environmental Science and Pollution Research, 2018)

The variation of cloud amount and light rainy days under heavy pollution over South China during 1960–2009 - Chuanbo Fu; Li Dan (Environmental Science and Pollution Research, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Complexity measure of regional seasonal precipitation series based on wavelet entropy - Dong Liu; Qiang Fu; Dan Zhao; Tianxiao Li (Hydrological Sciences Journal, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Adhesion of bone marrow mesenchymal stem cells on porous titanium surfaces with strontium-doped hydroxyapatite coating - Dan-Li Fu; Qiao-hong Jiang; Fu-ming He; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

KIFC1 and myosin Va: two motors for acrosomal biogenesis and nuclear shaping during spermiogenesis of Portunus trituberculatus - Dan-Dan Ma; Meng-Ying Pan; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2017)

Variations in forest aboveground biomass in Miyun Reservoir of Beijing over the past two decades - Li Fu; Dan Zhao; Bingfang Wu; Zhihong Xu; Yuan Zeng (Journal of Soils and Sediments, 2017)

Tolerance and stress response of sclerotiogenic Aspergillus oryzae G15 to copper and lead - Dan-Dan Long; Rong-Rong Fu; Jian-Rong Han (Folia Microbiologica, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Role of the lipid-regulated NF-κB/IL-6/STAT3 axis in alpha-naphthyl isothiocyanate-induced liver injury - Zhong-Ze Fang; Naoki Tanaka; Dan Lu; Chang-Tao Jiang; Wei-Hua Zhang; Chunze Zhang; Zuo Du; Zhi-Wei Fu; Peng Gao; Yun-Feng Cao; Hong-Zhi Sun; Zhi-Tu Zhu; et al. (Archives of Toxicology, 2017)

Measurement and modeling of nitrous and nitric oxide emissions from a tea field in subtropical central China - Dan Chen; Yong Li; Cong Wang; Xiaoqing Fu; Xinliang Liu; Jianlin Shen; Yi Wang; Runlin Xiao; De Li Liu; Jinshui Wu (Nutrient Cycling in Agroecosystems, 2017)

Effects of selenite and selenate application on distribution and transformation of selenium fractions in soil and its bioavailability for wheat (Triticum aestivum L.) - Fayaz Ali; Qin Peng; Dan Wang; Zewei Cui; Jie Huang; Dongdong Fu; Dongli Liang (Environmental Science and Pollution Research, 2017)

Dibenzo-α-pyrones from the endophytic fungus Alternaria sp. Samif01: isolation, structure elucidation, and their antibacterial and antioxidant activities - Jin Tian; Linyun Fu; Zihao Zhang; Xuejiao Dong; Dan Xu; Ziling Mao; Yang Liu; Daowan Lai; Ligang Zhou (Natural Product Research, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

Complexity measurement of regional groundwater resources system using improved Lempel-Ziv complexity algorithm - Dong Liu; Dan Zhao; Qiang Fu; Qiuchen Wu; Yongjia Zhang; Tianxiao Li; Khan M Imran; Faiz M Abrar (Arabian Journal of Geosciences, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Analysis of the Appropriate Development Scale of Regional Paddy Field Under the Restriction of Water Resources - Dong Liu; Dan Zhao; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Wenting Liu; Faiz M. Abrar (Agricultural Research, 2016)

Diagnostic values of osteopontin combined with CA125 for ovarian cancer: a meta-analysis - Zhu Lan; Dan Fu; Xiuzhang Yu; Mingrong Xi (Familial Cancer, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Construction and pilot screening of a signature-tagged mutant library of Sinorhizobium fredii - Dan Wang; Yuan Chun Wang; Li Juan Wu; Jian Xin Liu; Pan Zhang; Jian Jiao; Hui Yan; Tao Liu; Chang Fu Tian; Wen Xin Chen (Archives of Microbiology, 2016)

Precipitation Complexity Measurement Using Multifractal Spectra Empirical Mode Decomposition Detrended Fluctuation Analysis - Dong Liu; Mingjie Luo; Qiang Fu; Yongjia Zhang; Khan M. Imran; Dan Zhao; Tianxiao Li; Faiz M. Abrar (Water Resources Management, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

An observational and modeling study of extratropical transition of Hurricane Sandy in 2012 - Dan Fu; Pengyuan Li; Gang Fu (Journal of Ocean University of China, 2015)

Developmental expression and localization of MHC class I molecules in the human central nervous system - Aifeng Zhang; Hong Yu; Youji He; Yuqing Shen; Ying Zhang; Jiane Liu; Bo Fu; Dan Lv; Fengqin Miao; Jianqiong Zhang (Experimental Brain Research, 2015)

Experimental evaluation of calcein and alizarin red S for immersion marking grass carp Ctenopharyngodon idellus - Hongjian Lü; Hongjun Chen; Mei Fu; Xiwen Peng; Dan Xi; Zhixin Zhang (Fisheries Science, 2015)

Performance of convective parameterization schemes in Asia using RegCM: Simulations in three typical regions for the period 1998–2002 - Shaukat Ali; Li Dan; Congbin Fu; Yang Yang (Advances in Atmospheric Sciences, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Occurrence and removal of six pharmaceuticals and personal care products in a wastewater treatment plant employing anaerobic/anoxic/aerobic and UV processes in Shanghai, China - Dan Wang; Qian Sui; Shu-Guang Lu; Wen-Tao Zhao; Zhao-Fu Qiu; Zhou-Wei Miao; Gang Yu (Environmental Science and Pollution Research, 2014)

Trends in the different grades of precipitation over South China during 1960–2010 and the possible link with anthropogenic aerosols - Chuanbo Fu; Li Dan (Advances in Atmospheric Sciences, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

Polymorphisms in MHC class Ia genes and resistance to IHNV in rainbow trout (Oncorhynchus mykiss) - Zhe Liu; Dan Dan Hu; Shu Juan Shao; Juan Yang; Jian Fu Wang; Jin Qiang Huang (Genes & Genomics, 2013)

Celastrol exerts synergistic effects with PHA-665752 and inhibits tumor growth of c-Met-deficient hepatocellular carcinoma in vivo - Hong-Lei Jiang; Jun-Zhe Jin; Dan Wu; Dong Xu; Guo-Fu Lin; Hao Yu; Dong-Yan Ma; Jian Liang (Molecular Biology Reports, 2013)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Polycyclic aromatic hydrocarbons in animal-based foods from Shanghai: bioaccessibility and dietary exposure - Ying-Xin Yu; Liang Chen; Dan Yang; Yu-Ping Pang; Shao-Huan Zhang; Xin-Yu Zhang; Zhi-Qiang Yu; Ming-Hong Wu; Jia-Mo Fu (Food Additives & Contaminants: Part A, 2012)

Comparison study between observation and simulation for sea fog over the Yellow Sea in May 2009 - Dan Fu; Shuai Wang; Delin Chen; Huaji Pang; Pengyuan Li (Journal of Ocean University of China, 2012)

Structural determination of two new triterpenoid saponins acylated with monoterpenic acid from Gymnocladus chinensis Baill. - Wen Qi; Dan Yuan; Lian-Mei Yang; Ke-Hui Xie; Tian-Zhi Cai; Rong Yang; Hong-Zheng Fu (Natural Product Research, 2012)

Methylation effect on chalcone synthase gene expression determines anthocyanin pigmentation in floral tissues of two Oncidium orchid cultivars - Xiao-Jing Liu; Yao-Nung Chuang; Chung-Yi Chiou; Dan-Chu Chin; Fu-Quan Shen; Kai-Wun Yeh (Planta, 2012)

Improved LASSO priors for shrinkage quantitative trait loci mapping - Ming Fang; Dan Jiang; Dandan Li; Runqing Yang; Weixuan Fu; Lijun Pu; Huijiang Gao; Guihua Wang; Liyun Yu (Theoretical and Applied Genetics, 2012)

The heterogeneity of Meiyu rainfall over Yangtze–Huaihe River valley and its relationship with oceanic surface heating and intraseasonal variability - Dan-Qing Huang; Yong-Fu Qian; Jian Zhu (Theoretical and Applied Climatology, 2012)

Fluorescence microscopic analysis of bone osseointegration of strontium-substituted hydroxyapatite implants - Dan-li Fu; Qiao-hong Jiang; Fu-ming He; Guo-li Yang; Li Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Heterogeneous mantle source and magma differentiation of quaternary arc-like volcanic rocks from Tengchong, SE margin of the Tibetan Plateau - Mei-Fu Zhou; Paul T. Robinson; Christina Yan Wang; Jun-Hong Zhao; Dan-Ping Yan; Jian-Feng Gao; John Malpas (Contributions to Mineralogy and Petrology, 2012)

Constraining the mid-crustal channel flow beneath the Tibetan Plateau: data from the Nielaxiongbo gneiss dome, SE Tibet - Dan-Ping Yan; Mei-Fu Zhou; Paul T. Robinson; Djordje Grujic; John Malpas; Allen Kennedy; Peter H. Reynolds (International Geology Review, 2012)

Berberine cooperates with adrenal androgen dehydroepiandrosterone sulfate to attenuate PDGF-induced proliferation of vascular smooth muscle cell A7r5 through Skp2 signaling pathway - Jia Liu; Jian Xiu; Junxian Cao; Qianping Gao; Dan Ma; Lu Fu (Molecular and Cellular Biochemistry, 2011)

cDNA cloning and characterization of UDP-glucose: anthocyanidin 3-O-glucosyltransferase in Freesia hybrida - Xin Sui; Xiang Gao; Man Ao; Qinmei Wang; Dan Yang; Meng Wang; Yang Fu; Li Wang (Plant Cell Reports, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Important Role of Catalase in the Production of β-carotene by Recombinant Saccharomyces cerevisiae under H2O2 Stress - Guo-liang Yan; Heng-yu Liang; Zhi-qun Wang; Xiao-fan Yang; Dan Liu; Jin-fu Liu; Chang-qing Duan (Current Microbiology, 2011)

Microcalorimetric study of the effect of Benzoinum and Styrax on the growth of Escherichia coli - Jian Wang; Danhong Cheng; Nan Zeng; Houlin Xia; Yong Fu; Dan Yan; Yanling Zhao; Xiaohe Xiao (Natural Product Research, 2011)

A chimeric peptide that binds to titanium and mediates MC3T3-E1 cell adhesion - Dan Wang; Jing Mao; Bin Zhou; Xiao-Fu Liao; Shi-Qiang Gong; Yan Liu; Jing-Tao Zhang (Biotechnology Letters, 2011)

Seasonal variation, source, and regional representativeness of the background aerosol from two remote sites in western China - Wenjun Qu; Dan Wang; Yaqiang Wang; Lifang Sheng; Gang Fu (Environmental Monitoring and Assessment, 2010)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Infection and replication of avian influenza H5N1 virus in an infected human - Jing-Jiao Zhou; Dan-Yun Fang; Jie Fu; Jiang Tian; Jun-Mei Zhou; Hui-Jun Yan; Yu Liang; Li-Fang Jiang (Virus Genes, 2009)